Carbon nanotube, carbon nanotube dispersion liquid, secondary battery using same, and method for producing carbon nanotube
By controlling the volume density and Zr content of carbon nanotubes and combining with appropriate crushing conditions, a carbon nanotube dispersion liquid with excellent dispersion and conductivity is prepared, which solves the problem of difficulty in diffusion and uniform dispersion of carbon nanotubes in the dispersion medium, and achieves efficient conductive network formation and improvement of secondary battery performance.
Patent Information
- Application Number
- CN202480002905.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-31
- Filing Date
- 2024-06-17
- Publication Date
- 2025-02-28
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a carbon nanotube and a method for manufacturing the carbon nanotube.
[0002] More specifically, the present invention relates to a carbon nanotube dispersion, a carbon nanotube resin composition comprising the carbon nanotube dispersion and a binder resin, a composite slurry comprising the carbon nanotube dispersion, the binder resin and an active substance, an electrode film formed from the composite slurry, and a secondary battery comprising the electrode film. Background Art
[0003] Carbon nanotubes have a cylindrical graphite layer structure, are chemically stable, and have electrical conductivity and mechanical toughness, so they are used in various applications such as electronic materials, structural materials, and coatings. Specific uses of carbon nanotubes include electronic materials, semiconductor materials, filler materials, short needle probes for microscopes, adsorbent materials, and filter materials.
[0004] Among them, electrode materials using carbon nanotubes are expected to be applied to secondary batteries, fuel cells, electric double layer capacitors, and the like because of their excellent electrical conductivity.
[0005] With the popularity of electric vehicles, the miniaturization, lightness and high performance of mobile phones, a secondary battery with high energy density is sought, and then the high capacity of the secondary battery is sought. In this context, due to the characteristics of high energy density and high voltage, non-aqueous electrolyte secondary batteries using non-aqueous electrolytes, especially lithium-ion secondary batteries, are used in a large number of devices.
[0006] The electrode of the secondary battery is made by coating the collector with a composite material slurry containing a positive electrode active material or a negative electrode active material, a conductive material, a binder resin, etc. As a conductive agent, carbon black, graphene, fine carbon materials, etc. are used. In order to further improve the conductivity and improve the capacity of the battery, the use of carbon nanotubes as a kind of fine carbon fiber is being studied. For example, by adding carbon nanotubes to the positive electrode, the conductivity of the electrode film can be improved and the electrode resistance can be reduced. Among them, multi-layer carbon nanotubes with an outer diameter of several nm to several 10nm are relatively cheap and are being put into practical use. If carbon nanotubes with a small average outer diameter and a large fiber length are used, a conductive network can be efficiently formed even in a small amount, and a high capacity of the secondary battery can be achieved. On the other hand, the carbon nanotubes with these characteristics have strong cohesion, and it is difficult to further improve the dispersibility of the carbon nanotube dispersion.
[0007] Patent document 1 proposes the following: by determining the wettability index of the mass of the solvent absorbed relative to the mass of the carbon nanotubes, a high-concentration and low-viscosity carbon nanotube dispersion containing more than 2% by mass of carbon nanotubes is provided. In patent document 1, the wettability index is controlled by dry-crushing the carbon nanotubes using a grinding device containing metal balls or ceramic balls. In a specific example, a batch dry crushing is performed for 10 minutes to 140 minutes using a mill. In addition, patent document 2 proposes the following carbon nanotube coating: using carbon nanotubes with a determined average outer diameter and surface oxygen concentration, a black color and glossiness are imparted to a resin molded body or a car body. In patent document 2, the surface oxygen concentration of the carbon nanotubes is controlled by crushing untreated carbon nanotubes using a crushing medium without intervening a liquid medium.
[0008] Patent document 3 discloses a conductive material dispersion, which includes: a dispersant containing a specific copolymer, a conductive material, and a dispersion medium. Patent document 3 proposes the following: by appropriately controlling the dispersion state so that the phase angle of the conductive material dispersion at a frequency of 1 Hz obtained by dynamic viscoelasticity measurement is within a specified range, a conductive material dispersion is provided in which even high-concentration carbon fibers are well dispersed in the dispersion medium. In addition, patent document 4 discloses a conductive material dispersion, which includes: a conductive material, a dispersant, and an amide-based organic solvent. Patent document 4 proposes the following: by appropriately controlling the dispersion state so that the pH of the conductive material dispersion, the phase angle at a frequency of 1 Hz obtained by dynamic viscoelasticity measurement, and the complex elastic modulus are within a specified range, a conductive material dispersion is provided that can achieve good dispersibility, stability, operability, and all of these coexist.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Korean Patent No. 10-2125933
[0012] Patent Document 2: Japanese Patent Application Publication No. 2020-029372
[0013] Patent Document 3: Japanese Patent Application Publication No. 2022-042689
[0014] Patent Document 4: Japanese Patent Application Publication No. 2022-042691 Summary of the invention
[0015] Problems to be solved by the invention
[0016] When carbon nanotubes are dispersed in a dispersion medium, the carbon nanotubes have a high aspect ratio and are physically strongly bonded to each other due to van der Waals forces. Therefore, the carbon nanotubes are difficult to diffuse in the dispersion medium due to entanglement or difficulty in untangling bundles.
[0017] In addition, by dispersing carbon nanotubes in a dispersion medium, the dispersion liquid becomes highly viscous, so it is difficult to obtain a dispersion liquid containing a high concentration of uniformly dispersed carbon nanotubes, and it is particularly difficult to obtain a high-concentration dispersion liquid that takes into account both fluidity and storage stability. In order to eliminate the difficulty in dispersion caused by the high aspect ratio inherent in carbon nanotubes, the following technology is disclosed: as in Patent Document 1 or Patent Document 2, the carbon nanotubes are dry-treated using a pulverizing medium to improve the wettability of the carbon nanotubes with respect to the solvent, thereby obtaining a carbon nanotube dispersion liquid having a low viscosity even at a high concentration of 2% by mass or more of the carbon nanotubes. However, there is still room for research in order to fully form a developed conductive network derived from the high aspect ratio inherent in the carbon nanotubes in an electrode film using carbon nanotubes.
[0018] Patent Documents 3 and 4 disclose the following technology: in addition to controlling the composition (type of dispersant, etc.) or pH of the conductive material dispersion, the physical properties of the conductive material dispersion, such as the phase angle or complex elastic modulus, are controlled, thereby dispersing the carbon nanotubes as the conductive material at a high concentration. However, there is still room for research on the processing method of the carbon nanotubes themselves or the temporal stability of the conductive material dispersion.
[0019] That is, the problem to be solved by the present invention is to provide a carbon nanotube with high dispersibility and storage stability, and to provide a composite material slurry with excellent fluidity and dispersion stability of a carbon nanotube dispersion and good dispersibility when mixed with an active material. More specifically, to provide an electrode film with excellent adhesion to a collector and a secondary battery with high output, high capacity and long life, and an electrode film used for the secondary battery.
[0020] Technical means of solving problems
[0021] In order to take into account the fluidity and storage stability of the dispersion containing carbon nanotubes, it is important to eliminate the high aspect ratio of carbon nanotubes and improve the wettability of carbon nanotubes. On the other hand, in order to fully form a developed conductive network in the electrode film using carbon nanotubes, it is important to disperse while maintaining the high aspect ratio inherent in carbon nanotubes to a certain extent, and the fluidity, storage stability and conductivity of the dispersion are in a compromise relationship. The inventors and others have made great efforts to solve the above-mentioned problems, and found that by making the volume density of carbon nanotubes and the Zr content contained in the carbon nanotubes respectively within an appropriate range, the conductive network can be fully formed when the conductive film is formed while maintaining the wettability of carbon nanotubes (CNT) in the dispersion medium. In addition, it is found that by carefully controlling the pulverization conditions so that the volume density of carbon nanotubes and the Zr content contained in the carbon nanotubes are both within an appropriate range for dry treatment, the fluidity, storage stability and conductivity of the dispersion containing CNT obtained can be established.
[0022] By using carbon nanotubes according to some embodiments of the present invention, a carbon nanotube dispersion, a carbon nanotube resin composition, and a composite material slurry that take into account both fluidity and storage stability can be provided. Furthermore, by using a composition with good dispersion of these carbon nanotubes, an electrode film with a developed conductive network can be obtained, and a secondary battery with high output, high capacity, and long life can be provided.
[0023] In addition, the carbon nanotubes according to some embodiments of the present invention have high dispersibility and can maintain fluidity and storage stability even when a dispersion containing a high concentration of carbon nanotubes is prepared. Therefore, the carbon nanotubes can be uniformly contained in the electrode film and the secondary battery at a high concentration, and a secondary battery with higher output and high capacity can be provided.
[0024] That is, the present invention includes the following embodiments. The embodiments of the present invention are not limited to the following.
[0025] [1] A carbon nanotube, wherein the volume density X is 0.095 g / cm 3 Above and 0.125g / cm 3 Hereinafter, the Zr content is 5 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the following formula (5) is 8.0 or more.
[0026] Y=W / V···Formula (5)
[0027] (In formula (5), V is the mass (g) of the carbon nanotubes, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotubes when N-methyl-2-pyrrolidone is added dropwise to the carbon nanotubes of V (g) at 25°C)
[0028] [2] The carbon nanotube according to [1], wherein the volume density X (g / cm 3 ) and the maximum solvent absorption capacity Y of the carbon nanotubes satisfy all of the following equations (1) to (4).
[0029] Y≦-200X+37···Formula (1)
[0030] Y≧200X-17···Formula (2)
[0031] Y≧-200X+27···Formula (3)
[0032] Y≦200X+7···Formula (4)
[0033] [3] The carbon nanotube according to [1] or [2], wherein the average fiber length is 0.2 μm or more and 1.1 μm or less.
[0034] [4] The carbon nanotube according to [1] or [2], wherein the average fiber length is 0.2 μm to 1.0 μm, and the Zr content is 15 ppm to 200 ppm.
[0035] [5] A carbon nanotube dispersion comprising the carbon nanotube according to any one of [1] to [4] above, a dispersant, and a non-aqueous dispersion medium.
[0036] [6] The carbon nanotube dispersion according to [5], wherein the coefficient of determination R of the regression line represented by the following formula (I) is 2 is greater than 0.85, the slope a is 2≦a<20, and the y slice b is -5≦b<10.
[0037] y=ax+b ···Formula (I)
[0038] (Formula (1) is a regression line obtained by the least square method from a scatter plot with x as the horizontal axis and y as the vertical axis, obtained by measuring the carbon nanotube dispersion liquids stored at 40°C for 1 day, 40°C for 7 days, and 40°C for 14 days, respectively.
[0039] The number of days elapsed by static storage is i, and the static storage temperature is 40° C. The resin composition for secondary battery is cut at 25° C. and a cutting speed of 1.0 s. -1 The shear viscosity under i (Pa·s), and the complex elastic modulus at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement is defined as G * i (Pa),
[0040] x is at 25°C and cutting speed is 1.0s-1 The shear viscosity η i The natural logarithm of (Pa·s) (ln(η i )),
[0041] y is the complex elastic modulus G at 25°C and frequency 1 Hz * i (Pa),
[0042] i is 1, 7 and 14 when the production day of the carbon nanotube dispersion is set to day 0)
[0043] [7] A carbon nanotube resin composition comprising the carbon nanotube dispersion according to [5] or [6] and a binder resin.
[0044] [8] A composite material slurry comprising the carbon nanotube dispersion according to any one of [5] to [7] above, a binder resin, and an active material.
[0045] [9] An electrode membrane formed from the composite material slurry according to [8].
[0046]
[10] A secondary battery comprising a positive electrode and a negative electrode, wherein at least one of the positive electrode and the negative electrode has the electrode film according to [9].
[0047]
[11] A method for producing carbon nanotubes, comprising the step of dry-grinding the carbon nanotubes using a grinding device containing a grinding medium made of metal or ceramic material, wherein the dry-grinding is a through-grinding or circulating-grinding method, and the volume density X of the carbon nanotubes after dry-grinding is 0.095 g / cm 3 Above and 0.125g / cm 3 Hereinafter, the Zr content is 5 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the following formula (5) is 8.0 or more.
[0048] Y=W / V···Formula (5)
[0049] (In formula (5), V is the mass (g) of the carbon nanotubes, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotubes when N-methyl-2-pyrrolidone is added dropwise to the carbon nanotubes of V (g) at 25°C)
[0050]
[12] The method for producing carbon nanotubes according to
[11] , wherein the rate of change between the bulk density X after dry pulverization and the bulk density X′ before dry pulverization is not less than -60% and not more than 1000%.
[0051] Volume density change rate (%) = (X / X'-1) × 100
[0052]
[13] The method for producing carbon nanotubes according to
[11] or
[12] , wherein the rate of change between the powder resistance value Re after dry pulverization and the powder resistance value Re' before dry pulverization is 1% or more and 20% or less.
[0053] Powder resistance change rate (%) = (Re / Re'-1) × 100
[0054]
[14] The method for producing carbon nanotubes according to any one of
[11] to
[13] , wherein the pulverizing medium is zirconia beads, and the bead diameter of the zirconia beads is greater than 5 mm and less than 10 mm.
[0055]
[15] The method for producing carbon nanotubes according to any one of
[11] to
[14] , wherein the average fiber length of the carbon nanotubes after dry pulverization is 0.2 μm or more and 1.1 μm or less.
[0056]
[16] The method for producing carbon nanotubes according to any one of
[11] to
[15] , wherein the average fiber length of the carbon nanotubes after dry grinding is greater than 0.2 μm and less than 1.0 μm, and the Zr content is greater than 15 ppm and less than 200 ppm.
[0057]
[17] A method for producing a carbon nanotube dispersion, comprising the step of mixing and dispersing the carbon nanotube according to any one of
[11] to
[16] with a dispersant and a non-aqueous dispersion medium.
[0058] Effects of the Invention
[0059] According to an embodiment of the present invention, a carbon nanotube showing excellent dispersibility can be provided, and by using the carbon nanotube, a carbon nanotube dispersion having excellent fluidity and high dispersion stability and storage stability can be provided. In addition, according to another embodiment of the present invention, a carbon nanotube resin composition showing excellent fluidity and storage stability when mixed with a binder resin can be provided, and a composite material slurry for secondary battery electrodes can be provided, wherein the composite material slurry for secondary battery electrodes has excellent dispersibility of carbon nanotubes even after mixing with an active material, so it is not easy to produce agglomerates or sediments of carbon nanotubes and can exert high conductivity when an electrode film is formed. According to another embodiment of the present invention, a secondary battery with high output, high capacity and long life can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] [ Figure 1 ] is a graph plotting the natural logarithm (ln(η)) of the shear viscosity η (Pa·s) and the complex elastic modulus G obtained by measuring the carbon nanotube dispersion of the embodiment or the comparative example. *An example of a scatter plot of (Pa) and a regression line expressed by the least squares method from the scatter plot. DETAILED DESCRIPTION
[0061] Hereinafter, carbon nanotubes, carbon nanotube dispersions, carbon nanotube resin compositions comprising carbon nanotube dispersions and binder resins, composite slurries comprising carbon nanotube dispersions, binder resins and active materials, electrode films formed from composite slurries, and secondary batteries comprising the electrode films, as well as methods for manufacturing carbon nanotubes, are described in detail as embodiments of the present invention. The present invention is not limited to the following embodiments, and the present invention also includes embodiments implemented within the scope of the main purpose.
[0062] In addition, the carbon nanotube dispersion and the carbon nanotube resin composition containing the carbon nanotube dispersion and the binder resin refer to the state before the active substance is added. In this regard, the carbon nanotube dispersion and the carbon nanotube resin composition are distinguished from the composite slurry containing the active substance. That is, the carbon nanotube dispersion and the carbon nanotube resin composition do not substantially contain the active substance. This is a concept after excluding the state in which the active substance is intentionally added to the carbon nanotube dispersion and the carbon nanotube resin composition. Relative to the total mass of the carbon nanotube dispersion and the carbon nanotube resin composition, the active substance only needs to be 1% by mass or less, 0.5% by mass or less, or 0% by mass or less.
[0063] In this specification, carbon nanotubes may be referred to as “CNTs” and N-methyl-2-pyrrolidone may be referred to as “NMP (N-methyl-2-pyrrolidone)”. In addition, in this specification, a carbon nanotube dispersion may be referred to as a “CNT dispersion” or simply as a “dispersion”.
[0064] <<Carbon Nanotube>>
[0065] The volume density X of the carbon nanotubes of this embodiment satisfies 0.045 g / cm 3 Above and 0.125g / cm 3 The content of Zr is 3 ppm or more and 500 ppm or less.
[0066] Thus, the carbon nanotubes have excellent dispersibility, and a carbon nanotube dispersion using the carbon nanotubes can achieve both fluidity and storage stability.
[0067] More preferably, the carbon nanotubes preferably have a volume density X of 0.095 g / cm 3 Above and 0.125g / cm 3Hereinafter, the Zr content is 5 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the formula (5) described later is 8.0 or more. Thus, the filterability and acid stability of the carbon nanotube dispersion produced using the carbon nanotubes can be further improved.
[0068] From another perspective, the carbon nanotubes preferably have a volume density X of 0.045 g / cm 3 Above and 0.125g / cm 3 Below, the content of Zr is more than 3ppm and less than 500ppm, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by formula (5) described later is more than 14.0. Thus, dispersibility can be possessed in the CNT dispersion, and the battery performance can be further improved by the conductive network in the secondary battery. In the case described, the average fiber length of CNT is preferably more than 1.0μm, more than 1.5μm, or more than 1.9μm, and preferably less than 10μm, less than 5μm, or less than 2.0μm. Within these ranges, the conductivity and adhesion can be further improved by the conductive network in the secondary battery.
[0069] Regarding the filterability of the CNT dispersion, there is a tendency to decrease in the CNT dispersion due to tiny agglomerates derived from CNT or other resin components. Therefore, if the filterability is improved, the degree of disentanglement of CNT can also be improved. Thus, the conductive network can be more developed in the secondary battery. In addition, by improving the filterability, the effect of reducing the clogging in the filter can also be obtained in the respective manufacturing processes of the CNT dispersion, CNT resin composition, and composite material slurry.
[0070] In addition, about the acid stability of CNT dispersion, even if acid is added and the stability of CNT dispersion is good, there is a tendency to maintain good viscosity even over time. It is believed that one of the reasons is that acid acts on CNTs not adsorbed by dispersant in CNT dispersion to cause coagulation. Therefore, if acid stability is improved, the stability of CNT dispersion over time can also be improved. Thus, the conductive network can be more developed in the secondary battery.
[0071] The volume density X of CNT contributes to the wettability of the liquid medium, and when the CNT is treated by dry pulverization or the like, it can be used as one of the indicators of the degree of treatment of the CNT.
[0072] Among them, when using CNT as a conductive material in battery applications, one of the most important elements is to effectively utilize the high aspect ratio unique to CNT in the CNT dispersion. In the case of improving the wettability of the liquid medium of CNT by dry treatment, if the treatment intensity is too strong, the generation of CNT agglomerates is promoted. As a result, CNT cannot be fully untied in a non-aqueous solvent. In addition, the aspect ratio is reduced, resulting in concerns about reduced conductivity. In addition, it is also possible to disperse the CNT agglomerates with high intensity without performing CNT treatments such as dry pulverization, but due to the breakage of CNT fibers, the obtained dispersion has concerns about poor storage stability.
[0073] The volume density of CNT is 0.045g / cm 3 Above and 0.125g / cm 3 Hereinafter, the strength of CNT aggregation or the size of aggregates can be appropriately controlled. Furthermore, since CNT fibers can be appropriately dispersed in a non-aqueous solvent without breaking them and the desired conductivity can be maintained, a developed conductive network can be formed in the electrode film by using the dispersion to form an electrode film.
[0074] The volume density X of CNT is 0.045 g / cm 3 Above, preferably 0.050 g / cm 3 More preferably, 0.080 g / cm 3 In addition, it is 0.125g / cm 3 Below, preferably 0.125 g / cm 3 Below, more preferably 0.120 g / cm 3 Below, more preferably 0.110 g / cm 3 Below, particularly preferably 0.100 g / cm 3 the following.
[0075] From the viewpoint of appropriately controlling the strength of CNT aggregation, the size of aggregates, etc. and further improving filterability, the volume density X of CNT is more preferably 0.090 g / cm 3 More preferably, 0.095 g / cm 3 Above, can also be 0.097g / cm 3 Above, 0.099g / cm 3 Above, or 0.100g / cm 3 For example, the volume density X of CNT is more preferably 0.090 g / cm 3 Above and 0.125g / cm 3 Below, more preferably 0.095 g / cm 3 Above and 0.120g / cm 3Within these ranges, the filterability and acid stability of the CNT dispersion can be further improved.
[0076] The volume density X of CNT in the present disclosure is the relaxed volume density when sparsely packed. CNT is allowed to fall freely and placed in a container with an upper opening of a specified capacity until it overflows. In a static state, the raised CNT powder on the upper end surface is scraped flat with a scraper, and the mass of CNT is measured. The mass of CNT is divided by the volume of the container, thereby obtaining the volume density X.
[0077] As a specific method for measuring the bulk density X, for example, the CNT powder can be allowed to fall freely and be placed in a 30 ml stainless steel cylindrical container. After the raised portion of the upper end surface of the container is scraped flat, the mass of the CNT powder is obtained and divided by the volume of the container. In order to break up the agglomerates formed by the CNT powder during storage and allow the obtained sample to flow freely into the measurement container until it overflows, a sufficient amount of sample for the test is prepared by passing through a 0.5 mm sieve.
[0078] The Zr content in the CNT of the present embodiment is 3 ppm or more and 500 ppm or less.
[0079] It is preferably 400 ppm or less, more preferably 300 ppm or less, and still more preferably 200 ppm or less. It is also preferably 4 ppm or more, and more preferably 5 ppm or more.
[0080] With respect to the viewpoint of weakening the van der Waals force between CNTs and further improving the dispersion stability of CNTs, the Zr content contained in CNTs is more preferably more than 5ppm, and further preferably more than 10ppm, further preferably more than 15ppm, and may also be more than 20ppm, more than 30ppm, or more than 40ppm. For example, the Zr content contained in CNTs is preferably more than 5ppm and less than 500ppm, more preferably more than 10ppm and less than 300ppm, and further preferably more than 15ppm and less than 200ppm. Within these ranges, the dispersion stability can be further improved in the CNT dispersion, and the battery performance can be further improved.
[0081] The Zr content of CNT can be measured by inductively coupled plasma (ICP) emission analysis.
[0082] In addition, the Zr contained in CNT detected as the zirconium element in the ICP luminescence analysis method may be a substance (such as a pulverizing medium, etc.) used in a pretreatment process such as dry treatment of CNT, or may be due to the wear of the dispersing mechanism components, or may be a substance introduced by adding compounds such as zirconium oxide having zirconium to CNT. The Zr content of CNT can be adjusted by adjusting the type of dry pulverization medium or additives / coating agents, or dry pulverization treatment conditions (time or intensity, treatment temperature, etc.). In addition, the Zr contained in CNT can be reduced by centrifugation using the difference in specific gravity between CNT and Zr.
[0083] In addition, Zr has excellent toughness and heat resistance. In addition, most zirconium oxide exists in a size that cannot be graded with CNT, so it is difficult to remove all the mixed substances at once in any manufacturing process from CNT pretreatment to CNT dispersion, CNT resin composition containing the CNT dispersion, composite material slurry, and finally to secondary batteries. Therefore, it is particularly important to properly control the Zr content of CNTs in secondary battery applications by the method.
[0084] The carbon nanotubes according to some embodiments of the present invention are carbon nanotube compositions including Zr, thereby having excellent effects.
[0085] The reason why the dispersibility of CNTs is improved by setting both the bulk density X and the Zr amount within a predetermined range is not yet clear, but is presumed as follows.
[0086] It is speculated that by the presence of Zr, the van der Waals force between CNTs can be weakened and the dispersion stability of CNTs can be improved. By making the Zr content more than 3ppm, the CNTs forming the bundle structure are uniformly dispersed due to the van der Waals force, so there is no need to apply strong force, and the increase in the powder resistivity of CNTs and the volume resistivity of electrodes containing CNTs can be suppressed. In addition, by making the Zr content less than 500ppm, the adsorption of CNTs by the dispersant will not be hindered by the excessive Zr contained, thereby becoming an unstable dispersion state. In addition, the reduction in discharge capacity caused by the attachment of Zr to active materials, etc. can also be suppressed. It is more preferred that the Zr content is more than 5ppm and less than 500ppm.
[0087] On the other hand, as described above, the volume density contributes to the wettability of the liquid medium to the carbon nanotubes. By appropriately controlling the volume density, the CNTs can be uniformly and well dispersed while maintaining the length of the CNTs at a certain level or above, thereby forming a developed conductive network.
[0088] By setting both the bulk density and the Zr amount within predetermined ranges, it is possible to maximize the inherent conductivity of CNTs while achieving both the dispersibility and temporal stability of CNTs.
[0089] Furthermore, from the viewpoint of more finely controlling the state of CNT fibrillation and microscopically controlling the dispersibility in the CNT dispersion, the CNT of this embodiment preferably has a volume density of X (g / cm 3 ) and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the following formula (5) satisfy all of the following formulas (1) to (4).
[0090] Y≦-200X+37···Formula (1)
[0091] Y≧200X-17···Formula (2)
[0092] Y≧-200X+27··Formula (3)
[0093] Y≦200X+7··Formula (4)
[0094] Y=W / V···Formula (5)
[0095] (In formula (5), V is the mass (g) of the carbon nanotubes, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotubes when N-methyl-2-pyrrolidone is added dropwise to the carbon nanotubes of V (g) at 25°C)
[0096] The maximum solvent absorption capacity Y of CNT is defined by the above formula (5). The maximum solvent absorption capacity Y is the maximum mass of N-methyl-2-pyrrolidone absorbed by CNT per unit mass of CNT when CNT absorbs N-methyl-2-pyrrolidone. The maximum mass of N-methyl-2-pyrrolidone absorbed by CNT is the total mass of N-methyl-2-pyrrolidone added until N-methyl-2-pyrrolidone flows out of CNT powder when N-methyl-2-pyrrolidone is added dropwise to CNT powder.
[0097] Specifically, 5 g (V (g)) of CNT powder was placed in a cylindrical polypropylene container with a diameter of 10 mm by natural falling at 25°C, and N-methyl-2-pyrrolidone was dripped onto the surface of the CNT powder at a rate of 0.5 g at a time and at intervals of 1 minute while the container was left to stand. It was observed whether the droplets of N-methyl-2-pyrrolidone began to flow out to the surface of the CNT powder without being absorbed by the CNT powder. The total mass (g) of N-methyl-2-pyrrolidone dripped until the droplets of N-methyl-2-pyrrolidone began to flow out to the surface of the CNT powder was set to W (g).
[0098] The following describes equations (1) to (4). When the maximum solvent absorption capacity Y and the bulk density X are within the ranges determined by equations (1) to (4), the dispersibility and storage stability of CNTs can be further improved.
[0099] The maximum solvent absorption capacity Y is the maximum mass of N-methyl-2-pyrrolidone absorbed by CNT, but it is not limited to the type of dispersion medium, and there is a tendency as follows: the smaller the maximum solvent absorption capacity, the more the initial viscosity of CNT in the dispersion medium is suppressed, and the more it helps to improve the dispersibility. On the other hand, the volume density X is a factor that affects the dispersibility and storage stability of CNT in the dispersion medium. Although it is impossible to generalize, if the volume density becomes larger, it is easy to cause the sedimentation of CNT in the dispersion medium. If the volume density becomes smaller, the wettability of CNT in the dispersion medium decreases, and the dispersibility is easily reduced.
[0100] Focusing on the interaction between the maximum solvent absorption capacity Y and the volume density X, the carbon nanotubes are affected in the dispersion medium by the dispersibility and storage stability. The carbon nanotubes can be determined by the above formulas (1) to (4). When improving the dispersibility and storage stability of the carbon nanotubes, it is more preferable to defibrate the carbon nanotubes while maintaining a high aspect ratio and microdisperse them in the dispersion medium.
[0101] When the maximum solvent absorption capacity Y and the volume density X do not satisfy the formula (1), that is, when Y>-200X+37, there is a concern that the powder resistivity and electrode resistivity of CNT increase, and the battery performance decreases. Preferably, Y≦-200X+35, more preferably Y≦-200X+33.
[0102] When the maximum solvent absorption capacity Y and the volume density X do not satisfy the formula (2), that is, when Y < 200X-17, CNT aggregation or sedimentation occurs, and there is a concern that the electrode resistivity increases and the battery performance decreases. Preferably, Y ≥ 200X-13, and more preferably, Y ≥ 200X-9.
[0103] When the maximum solvent absorption capacity Y and the volume density X do not satisfy the formula (3), that is, when Y < -200X + 27, the CNT has poor dispersibility, and may aggregate or precipitate, and the battery performance may be reduced. Preferably, Y ≧ -200X + 29, and more preferably, Y ≧ -200X + 31.
[0104] When the maximum solvent absorption capacity Y and the volume density X do not satisfy formula (4), that is, Y>200X+7, the dispersibility of CNT is poor, the fluidity and storage stability of the CNT dispersion are reduced, and there is a concern that the battery performance will be reduced. Preferably, Y≦200X+3, more preferably Y≦200X-1.
[0105] The numerical range of the maximum solvent absorption capacity Y is not particularly limited. For example, the maximum solvent absorption capacity may be 5-22, 5-18, or 14-18. In another example, the maximum solvent absorption capacity may be 5-12, or 14-22.
[0106] From the viewpoint of further improving filterability and acid stability in the CNT dispersion, the maximum solvent absorption capacity Y is preferably 8.0 or more. More preferably, it is 8.4 or more, further preferably, it is 8.5 or more, and further preferably, it is 11.8 or more. For example, the maximum solvent absorption capacity Y may be 8.4 or more and 22 or less, 8.5 or more and 18 or less, or 11.8 or more and 12.7 or less.
[0107] From another perspective, the maximum solvent absorption capacity Y is preferably greater than 14. For example, it may be greater than 14 and less than 22, greater than 16 and less than 18, or greater than 17.1 and less than 17.5. Within these ranges, the dispersion stability can be further improved in the CNT dispersion, and the battery performance can be further improved.
[0108] CNT includes single-layer CNT and multi-layer CNT, which may exist in a mixed state. Single-layer CNT has a structure in which one layer of graphite is wound, and multi-layer CNT has a structure in which two or more layers of graphite are wound. In addition, the side wall of CNT may not be a graphite structure.
[0109] For example, a CNT including a sidewall having an amorphous structure is also referred to as a CNT in this specification. CNTs may be CNTs manufactured by any method. CNTs can generally be manufactured by laser ablation, arc discharge, thermal chemical vapor deposition (CVD), plasma CVD, and combustion, but are not limited thereto. In addition, CNTs may also be CNTs that have been surface treated. CNTs may also be CNT derivatives to which functional groups represented by carboxyl groups are given. In addition, CNTs containing organic compounds, metal atoms, or substances represented by fullerenes may also be used.
[0110] The average outer diameter of CNT is preferably 1 nm or more, more preferably 3 nm or more, and further preferably 5 nm or more. In addition, it is preferably 30 nm or less, more preferably 20 nm or less, and further preferably 15 nm or less. In addition, the average outer diameter of CNT can be calculated as follows: First, observe CNT using a transmission electron microscope and take a photo, select any 300 CNTs in the observation photo, and measure the outer diameter of each.
[0111] The average fiber length of CNT is preferably 0.1 μm or more, more preferably 0.2 μm or more, and more preferably 0.5 μm or more. In addition, it is preferably 5.0 μm or less, more preferably 2.0 μm or less, and more preferably 1.0 μm or less. In addition, the average fiber length of CNT can be calculated as follows: First, observe CNT using a scanning electron microscope and take a photo. In the observation photo, select any 300 CNTs and measure the fiber length of each.
[0112] From the perspective of further improving battery performance through the conductive network of the secondary battery, the average fiber length of CNT is more preferably 0.2 μm or more, and more preferably 0.5 μm or more, and more preferably 0.8 μm or more. From the perspective of further improving filterability and acid stability in the CNT dispersion, the average fiber length of CNT is more preferably 1.5 μm or less, and more preferably 1.1 μm or less, and more preferably 1.0 μm or less. For example, it can be 0.2 μm or more and 1.5 μm or less, 0.5 μm or more and 1.1 μm or less, or 0.8 μm or more and 1.0 μm or less, more preferably 0.2 μm or more and 1.1 μm or less, and more preferably 0.2 μm or more and 1.0 μm or less.
[0113] The value obtained by dividing the fiber length of CNT by the outer diameter is the aspect ratio. The representative aspect ratio can be obtained using the value of the average fiber length and the average outer diameter. The higher the aspect ratio of the conductive material, the higher the conductivity can be obtained when forming an electrode. The aspect ratio of CNT is preferably 30 or more, more preferably 50 or more, and more preferably 80 or more. In addition, it is preferably 10,000 or less, more preferably 3,000 or less, and more preferably 1,000 or less.
[0114] The specific surface area of CNT is preferably 100 m 2 / g or more, more preferably 150m 2 / g or more, more preferably 200m 2 / g or more. In addition, preferably 1200m 2 / g or less, more preferably 1000m 2 / g or less, more preferably 800m 2 / g or less. The specific surface area of CNT is calculated by the Brunauer-Emmett-Teller (BET) method based on nitrogen adsorption measurement. If the average outer diameter, average fiber length, aspect ratio, and specific surface area are within the above range, it is easy to form a developed conductive path in the electrode.
[0115] The carbon purity of CNT is represented by the content (mass %) of carbon atoms in CNT. Relative to 100 mass % of CNT, the carbon purity is preferably 80 mass % or more, more preferably 90 mass % or more, further preferably 95 mass % or more, and particularly preferably 98 mass % or more. By making the carbon purity within the above range, it is possible to prevent the formation of dendrites due to impurities such as metal catalysts, thereby causing adverse conditions such as short circuits.
[0116] In order to remove or reduce impurities such as metal catalysts and improve carbon purity, CNTs subjected to high-purity treatment may be used. The method of high-purity treatment is not particularly limited, and a known method may be used.
[0117] According to some embodiments, the CNT preferably has a volume density X of 0.095 g / cm 3 Above and 0.125g / cm 3 Hereinafter, the Zr content is 5 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the formula (5) described later is 8.0 or more, and the following (1) or (2) is satisfied. Thus, in the carbon nanotube dispersion prepared using the carbon nanotubes, the filterability and acid stability can be further improved.
[0118] (1) The average fiber length is 0.2 μm or more and 1.1 μm or less.
[0119] (2) The average fiber length is 0.2 μm or more and 1.0 μm or less, and the Zr content is 15 ppm or more and 200 ppm or less.
[0120] <Method for producing carbon nanotubes>
[0121] The CNT of this embodiment is not limited to its manufacturing method, and can be determined according to its physical property value, and can be prepared by pre-treating CNT manufactured according to a conventional manufacturing method or a known CNT. The pre-treatment method of CNT is not particularly limited to surface treatment or heat treatment using a reagent, and more than one pre-treatment method can be used together, preferably at least pulverization treatment. By optimizing the pulverization treatment conditions, the physical properties of the carbon nanotubes can be controlled.
[0122] For example, the CNT of the present embodiment can be obtained by pulverizing CNT having easily accessible physical properties. As the pulverization process, any of wet pulverization and dry pulverization can be used, and a pulverization medium can also be used. In terms of the ease of controlling the physical properties of the CNT, dry pulverization is preferred, and dry pulverization using a pulverization medium is more preferred. The pulverization medium can use a pulverization medium such as a metal or ceramic material, without particular limitation.
[0123] The components put into the pulverizing device may be only untreated CNTs, but optional components such as lubricants, dispersants, surface treatment agents, etc. may be further added. Dry pulverization is preferred, but untreated CNTs and a liquid medium may be put into the pulverizing device as needed.
[0124] When a pulverizing device is used, the pulverizing treatment may be any of the treatment methods of batch type, pass type, circulation type, etc., but in terms of the ease of control of the physical property values of CNT, it is preferably a pass type or a circulation type, and more preferably a circulation type. The so-called batch type is a method of processing using only the main body of the dispersing device without using piping, etc. The so-called pass type is a method in which the main body of the pulverizing device includes a tank for supplying CNT via piping and a tank for receiving CNT, so that CNT passes through the main body of the pulverizing device. In addition, the so-called circulation type is a method in which the CNT that has passed through the main body of the dispersing device is returned to the tank for supplying CNT, and the treatment is carried out while circulating. In any method, the longer the treatment time is extended, the more the pulverizing treatment is carried out, so as long as the pass or circulation is repeated until the target state is reached, if the size of the tank or the treatment time is changed, the processing amount can be increased. As a specific pulverizing device, for example, a bead mill, a ball mill, a grinding mill, etc. can be cited, and a ball mill or a grinding mill is equivalent to batch treatment. As a through-type or circulating type pulverizing device, for example, a dry continuous pulverizing device including a high-speed rotating arm and a stirring pulverizing medium in a horizontal cylindrical tank can be used. In the case of using zirconium oxide beads as the pulverizing medium, from the perspective of adjusting the Zr content of CNT to an appropriate range, it is preferred to use a through-type or circulating type dry continuous pulverizing device.
[0125] In the pulverization process of the passing type or the circulating type, the input mass per unit time of the CNT put into the pulverizing device, the type of pulverizing medium, the diameter, the input amount, the pulverization process temperature, etc., can obtain the desired CNT. In one example, it is advisable to use a circulating bead mill and put into CNT for dry pulverization. As a method for controlling the pulverization process temperature, there is a method for cooling using a cooling jacket provided in the pulverizing chamber body, a method for cooling outside the system of the bead mill, and a method for cooling with these two methods. From the viewpoint of cooling efficiency, it is preferably a method for cooling using a cooling jacket provided in the pulverizing chamber body. In addition, the pulverization process temperature can be measured by setting a thermometer in any piping, specifically, the powder outlet temperature measured by setting a thermometer at the outlet of the bead mill can be confirmed.
[0126] In the case of dry pulverization using a pulverizing medium, the pulverizing medium is preferably a ceramic material, and zirconium oxide is more preferably used in terms of not mixing metal impurities such as iron into CNT and pulverizing treatment strength. The pulverizing medium diameter is preferably more than 1mm, more preferably more than 3mm, and more preferably more than 5mm. By having a pulverizing medium diameter of more than the range, the collision energy to CNT becomes larger, and the dry pulverizing efficiency can be improved. In addition, the pulverizing medium diameter is preferably less than 15mm, more preferably less than 10mm, and more preferably less than 8mm. By having a pulverizing medium diameter of less than the range, the wear caused by the collision of the pulverizing media can be reduced. In addition, the pulverizing medium used in the dry pulverization of CNT is worn or broken by repeated use, which may become the cause of poor dispersion or contamination. Therefore, it is preferably used after grading and cleaning the pulverizing medium.
[0127] When zirconia beads are used as the grinding medium, from the perspective of more appropriately adjusting the Zr content of CNT, the bead diameter is preferably more than 5 mm and less than 10 mm. If two or more beads with greatly different bead diameters are used in combination, the beads are worn due to collisions between the beads, and a large amount of Zr is easily mixed into the CNT, so the bead diameter is preferably set to within ±1 mm. Since the tendency becomes stronger in a bead mill for dry grinding, it is preferred to use a zirconia bead when a bead mill is used, and more preferably the bead diameter of the zirconia bead is ±1 mm.
[0128] Here, the necessity and effect of pretreatment of CNTs, particularly dry treatment, will be described in detail.
[0129] If the CNT dispersion is prepared while maintaining the length, i.e., maintaining a high aspect ratio, the wettability of the CNT in the dispersion medium is low due to the high volume of the CNT, and the operation becomes poor, and there is a concern that the viscosity of the dispersion increases or the uniformity decreases. In addition, the composite material slurry manufactured using this CNT dispersion also becomes highly viscous and non-uniform, and there is a concern that the coating property of the electrode film decreases or the uniformity of the electrode film decreases.
[0130] On the other hand, if the volume density becomes too large due to pretreatment, the preparation of CNT dispersion (specifically, the wettability of the packing or the dispersion medium, etc.) becomes easy, and the finished viscosity of the dispersion tends to be lower, but due to the increase in the specific surface area of CNT, a large amount of dispersant is required to obtain sufficient stability, so it is not preferred from the perspective of the design of the electrode film. In addition, CNTs in a coagulated state with a large volume density or CNTs dispersed with high intensity and folded short to unravel the coagulation are difficult to form a developed conductive network, and there is a worry about the deterioration of conductivity. Furthermore, if the viscosity of the composite material slurry becomes too low, migration occurs in the drying process when the electrode film is made, and there is a worry that the electrode film becomes uneven. Furthermore, in the case of pre-treating CNT to a degree where the volume density becomes too large, there is a worry that the adsorption of CNT by the dispersant is hindered by Zr, and in addition, there is a worry about the reduction of the discharge capacity caused by the attachment of Zr to the active material, etc.
[0131] In view of these circumstances, by obtaining CNTs with appropriately controlled volume density and Zr content, a CNT dispersion with excellent dispersibility, stability, and conductivity can be achieved, and an electrode film with a developed conductive network can be obtained, thereby providing a secondary battery with high output, high capacity, and long life.
[0132] By adjusting the volume density X of CNT to 0.045 g / cm 3 ~0.125g / cm 3 The Zr content of CNT is adjusted to the range of 3ppm to 500ppm, and CNT with excellent performance can be obtained. More preferably, the volume density X of CNT is adjusted to 0.095g / cm 3 ~0.125g / cm 3 The range of , and the Zr content of CNT is adjusted to the range of 5ppm to 500ppm, and the maximum solvent absorption capacity Y is adjusted to be greater than 8.0.
[0133] Furthermore, the present inventors have discovered that when dry treatment is used as a pretreatment of CNTs, it is necessary to improve wettability to a certain extent while maintaining the high aspect ratio of CNTs to a certain extent. Therefore, as an indicator of the degree of treatment of CNTs, in other words, as an indicator of the end point of the dry treatment of CNTs, the volume density X of CNTs and the Zr content of CNTs are set within the above range, thereby obtaining CNTs with excellent dispersibility and conductivity.
[0134] That is, when dry treatment is used as a pretreatment of CNT, it is performed while managing the volume density X of CNT and the Zr content of CNT. The dry treatment conditions of CNT are preferably adjusted appropriately by evaluating the dispersibility of the CNT dispersion or the conductivity of the composite material slurry or electrode film using the CNT dispersion, but for the above reasons, the volume density X and Zr content can also be measured during the dry treatment, and these physical properties can be directly used as indicators for obtaining an ideal treatment state.
[0135] The change rate of the bulk density X after dry pulverization to the bulk density X' before dry pulverization is preferably -60% to 1000%, more preferably -20% to 500%, and further preferably -5% to 250%. By making the bulk density change rate within the above range, CNTs showing better dispersibility and high conductivity can be obtained.
[0136] The bulk density change rate was calculated by the following formula.
[0137] Volume density change rate (%) = (X / X'-1) × 100
[0138] The change rate of the powder resistance value Re after dry pulverization and the powder resistance value Re' before dry pulverization is preferably 1% or more and 20% or less, more preferably 2% or more and 18% or less, and further preferably 3% or more and 15% or less. By making the change rate of the powder resistivity within the above range, CNTs showing better dispersibility and high conductivity can be obtained.
[0139] The powder resistance value change rate was calculated by the following formula.
[0140] Powder resistance change rate (%) = (Re / Re'-1) × 100
[0141] The average fiber length of CNT after dry pulverization is preferably 0.1 μm or more and 5 μm or less, and may be 0.2 μm or more and 2 μm or less, or 0.5 μm or more and 1 μm or less. The fiber length of carbon nanotubes is 0.1 μm or more, which can further improve conductivity and toughness. In addition, by having a fiber length of carbon nanotubes of 1 μm or less, even if defibration is performed during the dispersion of CNT in a non-aqueous dispersion medium, the generation of agglomeration can be suppressed, thereby further preventing the viscosity of the dispersion from rising. In addition, the average fiber length of CNT before dry pulverization is not particularly limited, but for the reason that it is preferred to appropriately control the fiber length distribution of CNT by implementing dry pulverization, it is preferably 0.6 μm or more, more preferably 0.9 μm or more, and further preferably 1.2 μm or more. In addition, it is preferably 100 μm or less, more preferably 80 μm or less, and further preferably 60 μm or less. The average fiber length of CNT can be calculated by the method described. In addition, since it is preferable to change the dry treatment conditions and make appropriate adjustments according to the average outer diameter or average fiber length of the CNTs before dry treatment, the change rate of the average fiber length of the CNTs after dry grinding and the average fiber length of the CNTs before dry grinding is not particularly limited.
[0142] The untreated CNTs are not particularly limited, and may be CNTs produced by any method.
[0143] CNT can generally be manufactured by laser ablation, arc discharge, thermal CVD, plasma CVD and combustion, but is not limited to these. For example, in an environment where the oxygen concentration is less than 1% by volume, a carbon source and a catalyst are contacted and reacted at 500°C to 1000°C, thereby manufacturing CNT. In addition, any existing known raw gas can be used as the raw gas of the carbon source of untreated CNT. For example, as a raw gas containing carbon, hydrocarbons represented by methane, ethylene, propane, butane and acetylene, carbon monoxide, and alcohols can be used, but are not limited to these. In particular, from the perspective of ease of use, it is ideal to use at least any one of hydrocarbons and alcohols as a raw gas.
[0144] In addition, untreated CNTs usually exist as secondary particles. The shape of the secondary particles can be, for example, a state in which general primary particles, i.e., CNTs, are complexly entangled with each other. It can also be an aggregate of CNTs in a straight line. The secondary particles of an aggregate of linear CNTs are easier to loosen than substances entangled with each other. In addition, if compared with substances entangled with each other, the linear substances have good dispersibility, so they can be preferably used as CNTs. It is preferred that these untreated CNTs be pulverized to meet the desired physical property values.
[0145] Furthermore, the untreated CNT may be a surface-treated CNT. In addition, the CNT may be a CNT derivative to which a functional group represented by a carboxyl group is imparted. In the case of a pulverization treatment, these treatments may be performed before, after, at the same time, or at any time of a combination of these pulverization treatments.
[0146] In addition, the distribution of fiber length, pore diameter, etc. of untreated CNT varies depending on the type. Therefore, the compression of CNT and the folding method of CNT by dry pulverization and the like vary depending on the type of CNT. The distribution of various characteristics of the obtained CNT varies depending on the type of CNT and the treatment method, so it is advisable to apply an appropriate treatment method according to the type of CNT. For example, as a treatment method, it is sufficient to appropriately adjust the selection of the pulverization treatment device, the treatment time, etc.
[0147] <<Carbon Nanotube Dispersion Liquid>>
[0148] The CNT dispersion liquid of this embodiment includes the above-mentioned CNT, a dispersant, and a non-aqueous dispersion medium. The details of CNT are as described above.
[0149] <Dispersant>
[0150] The CNT dispersion liquid contains a dispersant. The dispersant is not particularly limited, and is preferably a dispersant that can stabilize the dispersion of CNT in the CNT dispersion liquid. The dispersant can use any of a resin-type dispersant and a surfactant, but in terms of strong adsorption to CNT and good dispersion stability, a resin-type dispersant is preferred. A dispersant of a suitable preferred type can be used in a preferred amount according to the characteristics required for the dispersion of CNT.
[0151] As the resin-type dispersant, (meth)acrylic acid-based polymers, polymers derived from ethylenically unsaturated hydrocarbons, cellulose-based derivatives, copolymers thereof, and the like can be used.
[0152] Examples of polymers derived from ethylenically unsaturated hydrocarbons include polyvinyl alcohol resins, polyvinyl pyrrolidone resins, polyacrylonitrile resins, nitrile rubbers, etc. Examples of polyvinyl alcohol resins include polyvinyl alcohol, modified polyvinyl alcohol having functional groups other than hydroxyl groups (e.g., acetyl, sulfonic, carboxyl, carbonyl, amino), polyvinyl alcohol modified with various salts, other polyvinyl alcohol modified with anions or cations, polyvinyl acetals modified with aldehydes (acetal modification or butyral modification, etc.) (polyvinyl acetal, polyvinyl butyral, etc.), etc. As the polyacrylonitrile resin, it can be a homopolymer of polyacrylonitrile, a copolymer of polyacrylonitrile, a modified body thereof, etc., preferably a polyacrylonitrile resin having at least one selected from the group consisting of hydroxyl, carboxyl, primary amino, secondary amino, and mercapto active hydrogen groups, basic groups, alkyl groups derived from (meth) acrylic acid alkyl esters or α-olefins, etc., for example, the acrylonitrile copolymers described in Japanese Patent Laid-Open No. 2020-163362 can be used. As nitrile rubbers, acrylonitrile butadiene rubber, hydrogenated acrylonitrile butadiene rubber, etc. can be listed. As cellulose derivatives, cellulose acetate, cellulose butyrate, cyanoethyl cellulose, ethyl hydroxyethyl cellulose, nitrocellulose, methyl cellulose, ethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, etc., or copolymers thereof, etc. In addition, the dispersants described in International Publication No. 2008 / 108360, Japanese Patent Laid-Open No. 2018-192379, Japanese Patent Laid-Open No. 2019-087304, Japanese Patent Laid-Open No. 2020-011934, and Japanese Patent Laid-Open No. 2009-026744 can be used, but are not limited to these. In particular, methylcellulose, ethylcellulose, polyvinyl alcohol, polyvinyl butyral, polyvinyl pyrrolidone, homopolymers of polyacrylonitrile, copolymers of polyacrylonitrile, and hydrogenated acrylonitrile butadiene rubber are preferred. Polymers into which other substituents are introduced in a part of these polymers, polymers after modification, etc. can also be used.
[0153] From the viewpoint of affinity balance between CNT as a dispersed object and a non-aqueous dispersion medium and tolerance to an electrolyte, the weight average molecular weight of the resin type dispersant is preferably 500,000 or less, more preferably 300,000 or less. In addition, it is preferably 3,000 or more, more preferably 5,000 or more. The resin type dispersant can be used alone or in combination of two or more. The weight average molecular weight is the weight average molecular weight calculated by gel permeation chromatography (GPC).
[0154] As commercially available polyvinyl alcohol-based resins, various grades can be obtained under trade names such as Kuraray Poval (polyvinyl alcohol resin manufactured by Kuraray), Gohsenol, Gohsenex (polyvinyl alcohol resin manufactured by Nippon Synthetic Chemical Industry), Denka Poval (polyvinyl alcohol resin manufactured by Denka), and J-Poval (polyvinyl alcohol resin manufactured by JAPAN VAM & POVAL). In addition, modified polyvinyl alcohols having various functional groups can also be obtained in the same manner. In addition, substances synthesized using known synthesis methods can also be used. Specific examples of commercially available polyvinyl pyrrolidone-based resins include Luvitec K17 (K value: 15.0 to 19.0, low molecular weight), K30 (K value: 27.0 to 33.0), K90 (K value: 88.0 to 92.0), and K90HM (K value: 92.0 to 96.0, high molecular weight) (manufactured by BASF Japan), K15, K30, K90, and K120 (manufactured by ISP), polyvinyl pyrrolidone K30 (K value: 27.0 to 33.0), K90 (K value: 88.0 to 96.0) (manufactured by Nippon Catalyst Co., Ltd.), PVP K12 (K value: 10 to 14), K15 (K value: 13 to 19), K30 (K26 to K35), K60 (K value: 50 to 62), and K90 (K value: 88 to 100) (manufactured by DSP Gokyo Food & Chemical Co., Ltd.). With regard to the viewpoint of preventing viscosity from rising, polyvinyl pyrrolidone is preferably 150 or less in K value, more preferably 100 or less in K value, and further preferably 85 or less in K value. As commercially available nitrile rubbers, the trade names such as Therban (hydrogenated nitrile rubber manufactured by Arlanxeo), Baymod (nitrile rubber manufactured by Arlanxeo), Zetpole (hydrogenated nitrile rubber manufactured by Japan Zeon), Nipole NBR (nitrile rubber manufactured by Japan Zeon) can be used to obtain nitrile ratio, hydrogenation rate, and various grades different from molecular weight. In addition, materials synthesized by known synthesis methods can also be used.
[0155] Surfactants may be used instead of or in addition to the resin-based dispersant. Surfactants can be classified into anionic, cationic, amphoteric ionic surfactants, and nonionic surfactants.
[0156] The CNT dispersion may further include an alkali. If an alkali is contained in the CNT dispersion, the wettability of the CNT in the dispersion medium is improved and the dispersibility or dispersion stability is improved, so it is preferred. The added alkali can be selected from at least one of the groups consisting of inorganic bases, inorganic metal salts, organic bases, and organic metal salts. Relative to the total amount of the CNT dispersion, these are preferably 0.001% to 0.1% by mass, and more preferably 0.005% to 0.05% by mass in total amount. If the amount of alkali added is too much, it may cause corrosion inside the dispersion device and / or the battery.
[0157] Here, the water content of the added alkali is preferably less than 5 mass %, more preferably less than 3 mass %, and further preferably less than 2 mass %. If a large amount of water is included in the added alkali, the adsorption of the dispersant to CNT is reduced, and there is a worry that it is difficult to stably exist CNT in the non-aqueous dispersion medium. By setting the water content to the range, it is possible to prevent the composite material slurry mixed with the active material from producing gelation problems or residual moisture in the positive electrode and the generation of acids such as hydrofluoric acid (HF) causing the deterioration of the positive electrode. There is the following problem, that is, residual moisture in the positive electrode and the generation of acids such as HF causing the deterioration of the positive electrode. In addition, if there is moisture in alkali metal hydroxides such as LiOH, the paste containing the positive active material is easily gelled when making the positive electrode, and there is also a problem that electrode formation becomes difficult.
[0158] As inorganic bases and inorganic metal salts, for example, chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, borates of alkali metals or alkaline earth metals; and ammonium hydroxide, etc. Among these, hydroxides or alcoholates of alkali metals or alkaline earth metals are preferred from the viewpoint of being able to easily supply cations. As hydroxides of alkali metals, for example, lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. can be mentioned. As hydroxides of alkaline earth metals, for example, calcium hydroxide, magnesium hydroxide, etc. can be mentioned. Among these, it is more preferred to use at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide. In addition, the metal possessed by the inorganic base may also be a transition metal.
[0159] Examples of the organic base include primary amine compounds, secondary amine compounds, tertiary amine compounds (alkylamines, amino alcohols, etc.) having 1 to 40 carbon atoms and optionally having a substituent, and organic hydroxides.
[0160] Examples of the primary alkylamine having 1 to 40 carbon atoms which may have a substituent include alkylamines such as propylamine, butylamine, isobutylamine, octylamine, 2-ethylhexylamine, and laurylamine; amino alcohols such as 2-aminoethanol and 3-aminopropanol; and 3-ethoxypropylamine.
[0161] Examples of the optionally substituted secondary alkylamine having 1 to 40 carbon atoms include alkylamines such as dibutylamine, diisobutylamine, N-methylhexylamine, and dioctylamine; and amino alcohols such as 2-methylaminoethanol.
[0162] Examples of the tertiary alkylamine having 1 to 40 carbon atoms which may have a substituent include alkylamines such as triethylamine, tributylamine, N,N-dimethylbutylamine, N,N-diisopropylethylamine, dimethyloctylamine, trioctylamine, and dimethyldecylamine, triethanolamine, and 2-(dimethylamino)ethanol.
[0163] The organic hydroxide is a salt containing an organic cation and a hydroxide ion. Examples of the organic hydroxide include trimethyl-2-hydroxyethylammonium hydroxide, tetramethylammonium hydroxide, trimethylphenylammonium hydroxide, 3-trifluoromethyl-phenyltrimethylammonium hydroxide, and benzyltrimethylammonium hydroxide.
[0164] Among these, from the viewpoint of the effect on CNTs, it is more preferable to use at least one selected from the group consisting of 2-aminoethanol, 3-aminopropanol, triethanolamine, and trimethyl-2-hydroxyethylammonium hydroxide.
[0165] As the organic metal salt, for example, alkali metal alkoxides, alkali metal acetates, etc. can be cited. As the alkali metal alkoxides, for example, lithium methoxide, lithium ethoxide, lithium propoxide, lithium tert-butoxide, lithium n-butoxide, sodium methoxide, sodium ethoxide, sodium propoxide, sodium tert-butoxide, sodium n-butoxide, potassium methoxide, potassium ethoxide, potassium propoxide, potassium tert-butoxide, potassium n-butoxide, etc. can be cited. Among these, sodium tert-butoxide is preferred from the viewpoint that cations can be easily supplied. In addition, the metal possessed by the organic base may also be a transition metal.
[0166] The CNT dispersion may further include an acid. If an acid is contained in the CNT dispersion, the polymerization of the resin and the viscosity increase and gelation of the composite material slurry for the positive electrode of a lithium ion battery accompanying it can be suppressed, so it is preferred. The added acid may be any of an inorganic acid and an organic acid. Relative to the total amount of the CNT dispersion, these are preferably 0.001% by mass to 1.0% by mass, more preferably 0.005% by mass to 0.5% by mass in total amount. If the amount of acid added is too much, there is a concern about reducing the adsorption and dispersion ability of the dispersant to CNT.
[0167] As inorganic acids, for example, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, etc. can be cited. As organic acids, carboxylic acid compounds, sulfonic acid compounds, etc. can be cited. As carboxylic acid compounds, formic acid, acetic acid, propionic acid, butyric acid, tartaric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, (methyl) acrylic acid, crotonic acid, fumaric acid, maleic acid, itaconic acid, citraconic acid, fluoroacetic acid, etc. can be cited. As sulfonic acid compounds, methanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, dinonylnaphthalenesulfonic acid, dinonylnaphthalene disulfonic acid, etc. can be cited. In addition, anhydrides, hydrates, or acids in which a portion of the acid is converted into salts can also be used. These can be used alone or in combination of two or more.
[0168] <Non-aqueous dispersion medium>
[0169] The CNT dispersion liquid contains a non-aqueous dispersion medium as a dispersion medium. The non-aqueous dispersion medium is not particularly limited, and is preferably a high dielectric constant solvent, preferably a solvent composed of any one of the high dielectric constant solvents, or a mixed solvent composed of two or more. In addition, one or more other solvents may be mixed in the high dielectric constant solvent for use.
[0170] As high dielectric constant solvents, the following can be used: amides (N-methyl-2-pyrrolidone (NMP), N-ethyl-2-pyrrolidone (NEP), N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylacetamide, N-methylcaprolactam, etc.); heterocyclics (cyclohexylpyrrolidone, γ-butyrolactone, etc.); sulfoxides (dimethyl sulfoxide, etc.); sulfones (hexamethylphosphoric acid triamide, cyclopentane sulfone, etc.); lower ketones (acetone, methyl ethyl ketone, etc.); carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, fluoroethylene carbonate, propylene carbonate, ethylene carbonate); and tetrahydrofuran; urea; acetonitrile, etc. The relative dielectric constant of the high dielectric constant solvent can be set to a value described in a solvent manual, etc., and is preferably 2.5 or more at 20°C.
[0171] From the perspective of the solubility of the dispersant or binder resin, or the wettability of CNTs with respect to the dispersion medium, the non-aqueous dispersion medium preferably contains an amide-based organic solvent, and more preferably contains at least one selected from the group consisting of N-methyl-2-pyrrolidone and N-ethyl-2-pyrrolidone.
[0172] The content of the amide organic solvent is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more relative to the total mass of the non-aqueous dispersion medium. From the perspective of handling, it is even more preferred to use N-methyl-2-pyrrolidone alone.
[0173] The CNT dispersion may contain any component such as a wetting agent, a wetting and penetrating agent, a leveling agent, or other additives as needed within the scope that does not hinder the purpose of the present invention. The optional component may be added at any time such as before the preparation of the CNT dispersion, during mixing, after mixing, or a combination thereof.
[0174] In terms of not substantially containing active materials even if any component is included within the range that does not hinder the purpose of the present invention, the content of CNT and dispersant in the CNT dispersion is 60% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and further preferably 95% by mass or more, based on the non-volatile component of the CNT dispersion, that is, the solid content of the CNT dispersion. In addition, it can be 100% by mass or less.
[0175] As other conductive materials other than CNT, carbon black may be included. Carbon black is preferably included in the CNT dispersion within the range that does not damage the effect of the present invention, and CNT is preferably 1% to 80% by mass, more preferably 1% to 50% by mass, relative to the total mass of carbon black and CNT. If the range is met, even if carbon black is included, the dispersion state of CNT can be controlled, and high dispersibility and fluidity can be maintained better. Furthermore, carbon black is preferably less than 20% by mass, more preferably less than 15% by mass, relative to the total mass of the CNT dispersion.
[0176] The stage of adding carbon black to the CNT dispersion is not particularly limited, and may be before, after, at the same time, or a combination of these. As another example of a method for manufacturing a CNT dispersion containing carbon black, there is a method of adding carbon black before, after, at the same time, or a combination of these to a binder resin added to a CNT dispersion. In the method, carbon black is preferably added in a state where CNTs are dispersed in the CNT dispersion. Alternatively, it may be a combination of these methods. That is, carbon black may also be further added before, after, at the same time, or in a combination of these to a binder resin added to a CNT dispersion containing carbon black.
[0177] <Method for producing CNT dispersion>
[0178] The CNT dispersion of the present embodiment is characterized in that it includes a process of mixing and dispersing the CNT with a dispersant and a non-aqueous dispersion medium. For example, it is preferred to use a dispersing device to disperse the CNT, the dispersant, and the non-aqueous dispersion medium and finely disperse them to produce. The dispersing device used for the treatment is not particularly limited. In addition, the dispersion treatment arbitrarily adjusts the timing of adding the materials used, and can be a multi-stage treatment of more than two times.
[0179] The dispersing device used when CNT is dispersed can be listed, for example: kneader, double-roll mill, three-roll mill, planetary mixer, ball mill, horizontal sand mill, vertical sand mill, annular bead mill, grinding machine, high shear mixer, high pressure homogenizer, ultrasonic homogenizer, etc. Wherein, in order to make CNT finely dispersed in CNT dispersion and obtain preferred dispersibility, it is preferred to use high shear mixer, high pressure homogenizer, ultrasonic homogenizer or these combinations and use. In particular, with respect to promoting the wetting of CNT, unraveling the viewpoint of coarse particles, it is preferred to use high shear mixer in the initial process of dispersion, and then with respect to the viewpoint of dispersing it under the state of maintaining the aspect ratio of CNT, it is preferred to use high pressure homogenizer. High pressure homogenizer is carried out in multiple stages by circulating dispersion, thus the dispersibility of CNT can be further improved. In addition, after being dispersed by high pressure homogenizer, bead mill is further used to disperse it, thus the dispersion state can be homogenized while maintaining the fiber length. In addition, in the CNT of some embodiments of the present invention in which wettability is improved by dry treatment, a high shear mixer is used in the initial step of dispersion, followed by dispersion by a bead mill, and then dispersion by a high-pressure homogenizer, thereby fully disentangling the CNT agglomerated with a certain force in the dry treatment, etc., and making the dispersion state uniform. When using a high-pressure homogenizer, the pressure of the homogenizing part of the high-pressure homogenizer is preferably 60MPa to 150MPa, and more preferably 60MPa to 120MPa.
[0180] There are batch dispersion, through dispersion, circulation dispersion, etc. in the dispersion method using a dispersion device, but any method can be used, and two or more methods can be combined. The so-called batch dispersion is a method of dispersing using only the dispersion device body without using piping, etc. Because of its simple operation, it is preferred in the case of small-scale production. The so-called through dispersion is a dispersion method in which the dispersion device body includes a tank for supplying the dispersed liquid via piping and a tank for receiving the dispersed liquid, and the dispersed liquid passes through the dispersion device body. In addition, the so-called circulation dispersion is a method of dispersing while circulating the dispersed liquid that passes through the dispersion device body. The longer the processing time is extended in any method, the more dispersion is performed. Therefore, as long as the passing or circulation is repeated until the target dispersion state is reached, the processing volume can be increased by changing the size of the tank or the processing time. Compared with the circulation dispersion, through dispersion is preferred in terms of the ease of making the dispersion state uniform. Compared with the through dispersion, the circulation dispersion is preferred in terms of the simplicity of operation or manufacturing equipment. The dispersion process sequentially or simultaneously performs the crushing of aggregated particles, the disentanglement, wetting, stabilization, etc. of the conductive material. Depending on the method of performing the process, the dispersion state of the finished product is different, so it is preferred to manage the dispersion state in each dispersion process by using various evaluation methods. For example, the method described in the embodiment can be used for management.
[0181] The dispersing device used when dispersing the CNT dispersion may also include a heat exchanger or a cooling liquid supply mechanism for cooling the CNT dispersion. By cooling the CNT dispersion or coarse dispersion that has been dispersed and has become high temperature in advance, the generation of bubbles in the CNT dispersion can be suppressed, and the residual solid components on the wall of the dispersion tank can be suppressed. The liquid temperature of the CNT dispersion is not particularly limited, and is preferably controlled at 25°C to 75°C, and more preferably controlled at 40°C to 65°C.
[0182] From the viewpoint of further microscopically controlling the dispersibility and fluidity of CNTs in the CNT dispersion, the regression line of the CNT dispersion of the present embodiment preferably has a coefficient of determination R 2 It satisfies 0.85 or above, the slope a satisfies 2≦a<20, and the y slice b satisfies -5≦b<10.
[0183] y=ax+b ···Formula (I)
[0184] (Formula (I) is a regression line obtained by the least square method from a scatter plot obtained by measuring a carbon nanotube dispersion liquid at a static storage temperature of 40°C for 1 day, 40°C for 7 days, and 40°C for 14 days, with x as the horizontal axis and y as the vertical axis. The number of days i elapsed after static storage and the static storage temperature of 40°C were set at 25°C and a cutting speed of 1.0 s. -1 The shear viscosity under i (Pa·s), and the complex elastic modulus at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement is defined as G* i (Pa), x is the shear viscosity η i The natural logarithm of (Pa·s) (ln(η i )), y is the complex elastic modulus G* at 25°C and frequency 1 Hz i (Pa), i is 1, 7 and 14 when the production day of the carbon nanotube dispersion is set to day 0)
[0185] By making the CNT dispersion liquid satisfy specific conditions in formula (I), the dispersion stability of CNT is excellent, even if due to the passage of time, the dispersibility and fluidity of the CNT dispersion liquid can be maintained. In addition, by using the CNT dispersion liquid, dispersibility and fluidity can also be maintained after further adding a binder resin, and then, a developed conductive network can be formed in the electrode film when the electrode film is made. And, thus, it is an electrode film with excellent adhesion to the collector, and then a secondary battery with high output, high capacity and high life can be made.
[0186] The CNT dispersion satisfying the specific conditions in formula (I) can be obtained by appropriately controlling the types and contents of CNTs, dispersants, and non-aqueous dispersion media, or the mixing conditions and dispersion conditions thereof. In particular, it is effective to appropriately control the volume density of CNTs and the Zr content in CNTs, for example, by using CNTs whose pretreatment conditions are optimized to satisfy formula (I), which can be used as an indicator for determining a good dispersion state in the CNT dispersion.
[0187] More specifically, CNTs with a volume density and Zr content within an appropriate range form a moderate aspect ratio and a cohesive state, so when dispersed, a CNT dispersion in which the CNTs are fully entangled with each other can be obtained. In addition, by not containing excessive Zr, a CNT dispersion with excellent storage stability can be obtained.
[0188] As described above, the dispersibility of CNTs in a CNT dispersion can be evaluated by the complex elastic modulus in the shear viscosity and dynamic viscoelasticity measurement, and the pretreatment method of CNTs is adjusted in a manner such that the shear viscosity and the complex elastic modulus of the CNT dispersion under specific conditions satisfy the relationship, so that even a CNT dispersion containing CNTs at a high concentration can maintain high dispersibility and fluidity. The regression line disclosed in the present invention can be measured and obtained using a CNT dispersion after being stored at 40°C for 1 day, 7 days, and 14 days.
[0189] The coefficient of determination R 2 If the ratio is less than 0.85, CNT aggregates are present in the CNT dispersion, and CNT aggregation or sedimentation occurs over time, which may reduce the adhesion of the electrode film or reduce the battery performance.
[0190] R 2 It is preferably 0.90 or more, and more preferably 0.95 or more.
[0191] Here, the coefficient of determination R 2 It can be calculated based on the square of the Pearson Product-Moment Correlation Coefficient.
[0192] The slope a may be 2≦a<20. When the slope a is less than 2, the CNTs in the CNT dispersion are present in an uneven state, and there is a concern that the adhesion of the electrode film is reduced or the battery performance is reduced. In addition, when the slope a is greater than 20, CNT aggregation or sedimentation occurs in the CNT dispersion, and there is a concern that the electrode resistance increases or the battery performance is reduced.
[0193] The slope a is preferably 2 or more, more preferably 5 or more, and further preferably 7 or more. The slope a is preferably less than 20, more preferably less than 15, and further preferably less than 14.
[0194] y slice b can be -5≦b<10. When y slice b is less than -5, the CNTs in the CNT dispersion are present in an uneven state, and there is a concern that the adhesion of the electrode film is reduced or the battery performance is reduced. In addition, when y slice b is greater than 10, CNT aggregation or sedimentation occurs in the CNT dispersion, and there is a concern that the electrode resistance increases or the battery performance is reduced.
[0195] y slice b is preferably not less than -5, more preferably not less than -3, and even more preferably greater than 0. In addition, y slice b is preferably less than 10, more preferably less than 8, and even more preferably less than 6.
[0196] By controlling the dispersion state of CNTs and preparing a CNT dispersion liquid that satisfies specific conditions of formula (I), the dispersion stability, stability over time, adhesion between the electrode film and the collector, and battery characteristics of the CNT dispersion liquid can be achieved.
[0197] i is the number of days that have passed by static storage, with the production date of the CNT dispersion being set to day 0, and is 1, 7, and 14. That is, regarding formula (I), a regression line can be obtained by using a CNT dispersion that has been statically stored at 40° C. for 1, 7, and 14 days from the production date, measuring the shear viscosity and the complex elastic modulus, and plotting the three points of x and y.
[0198] x is at 25°C and cutting speed is 1.0s -1 Shear viscosity η i The natural logarithm of (Pa·s) (ln(η i )). Here, the shear viscosity η i (Pa·s) represents the shear viscosity η (Pa·s) measured using the CNT dispersion after being stored at 40°C for i days.
[0199] y is the complex elastic modulus G* at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement i (Pa). Here, the complex elastic modulus G* i (Pa) represents the complex elastic modulus G* (Pa) measured using the CNT dispersion after being stored at 40°C for i days.
[0200] The shear viscosity η (Pa·s) of the CNT dispersion is 25°C and the cutting speed is 1.0 s. -1 The complex elastic modulus G* (Pa) is a value measured at 25° C. and a frequency of 1 Hz.
[0201] In detail, it can be measured by the method described in the embodiment. The shear rate of the CNT dispersion has a tendency to be smaller as the dispersibility of CNT is better, but in the case of a large fiber length of CNT, even if CNT is in a uniform and stably untied state in the medium, due to the structural viscosity of CNT itself, the value itself sometimes becomes higher. In addition, in addition to the dispersion state of CNT, it also changes due to the entanglement of CNT, dispersant, and other resin components, or the influence of these intermolecular forces, etc.
[0202] In addition, the complex elastic modulus represents the hardness of the CNT dispersion, and there is a tendency that the more favorable the dispersibility of CNT is and the lower the viscosity of the CNT dispersion is, the smaller the complex elastic modulus is. However, similarly to the shear viscosity, in the case of having the structural viscosity of CNT itself, even if CNT is in a state of being uniformly and stably untied in the medium, the CNT dispersion sometimes also becomes a high value. In addition, in addition to the dispersion state of CNT, it also changes due to the entanglement of CNT, dispersant, and other resin components, or the influence of these intermolecular forces, etc.
[0203] The temperature of CNT dispersion is 25℃ and the cutting speed is 1.0s -1 The shear viscosity η (Pa·s) under 0.05 is preferably greater than 0.05, more preferably greater than 0.20, and further preferably greater than 0.80. By setting the shear viscosity η within the above range, a CNT dispersion in which the CNTs are fully untied and uniformly dispersed can be obtained, and high composite material adhesion and excellent battery performance can be obtained.
[0204] In addition, the shear viscosity η is preferably 3.0 or less, more preferably 2.5 or less, and further preferably 2.0 or less. When the shear viscosity η is within the above range, a CNT dispersion liquid in which CNTs are stably dispersed without aggregation or sedimentation of CNTs can be obtained, and excellent battery performance can be obtained.
[0205] The complex elastic modulus G* (Pa) of the CNT dispersion at a temperature of 25°C and a frequency of 1 Hz is preferably 0.80 or more, more preferably 2.0 or more, and further preferably 4.0 or more. By having the complex elastic modulus G* within the above range, a CNT dispersion in which the CNTs are fully untied and uniformly dispersed can be obtained, and high composite material adhesion and excellent battery performance can be obtained.
[0206] In addition, the complex elastic modulus G* (Pa) is preferably 100.0 or less, more preferably 50.0 or less, and further preferably 10.0 or less. When the complex elastic modulus G* is within the above range, a CNT dispersion liquid in which CNTs are stably dispersed without CNT aggregation or sedimentation can be obtained, and excellent battery performance can be obtained.
[0207] In addition, the degree of disentanglement of CNT in CNT dispersion can also be evaluated by the filtration speed of CNT dispersion. More specifically, it can be evaluated by diluting CNT dispersion 3 times with non-aqueous dispersion medium and measuring the time for all the passages when CNT dispersion is subjected to vacuum filtration. It is believed that the reason is that in the case of tiny agglomerates derived from CNT or other resin components in CNT dispersion, the agglomerates cannot pass through the filter, or the filtration speed slows down. In addition, in the case where the dispersion state of CNT dispersion is unstable, if CNT dispersion is diluted with non-aqueous dispersion medium, it is easy to cause dispersion shock, and agglomerates are clearly confirmed, so similarly, it is impossible to pass through the filter, or the filtration speed slows down.
[0208] For the above reasons, the filtration rate can be used as an index for evaluating the dispersion state or dispersion stability of CNTs in the CNT dispersion liquid and the fluidity of the CNT dispersion liquid. More specifically, it can be measured by the method described in the Examples.
[0209] In addition, the fluidity and dispersion stability of the CNT dispersion can be evaluated by confirming the acid stability. More specifically, an acid can be added to the CNT dispersion, and the initial viscosity of the CNT dispersion containing the acid and the viscosity of the CNT dispersion containing the acid after being left to stand and stored for 7 days at 40°C are measured respectively, and the viscosity after being left to stand for 7 days at 40°C is evaluated relative to the rate of change of the initial viscosity. In the case where the CNT is stably dispersed, even if an acid is added to the CNT dispersion, the dispersibility of the CNT will not be destroyed, and a good viscosity is maintained even over time. On the other hand, even if the CNT in the initial stage appears to be in a good dispersed state, the dispersibility of the CNT is not sufficient. When the acid is added, the CNT that is not adsorbed by the dispersant condenses and causes poor dispersion, and the CNT dispersion increases in viscosity over time. By evaluating under this condition, the dispersion state or dispersion stability of the CNT in the CNT dispersion that takes into account the change over time can be evaluated. In more detail, it can be measured by the method described in the embodiment.
[0210] The average fiber length of CNT in the CNT dispersion is preferably 0.1 μm or more, more preferably 0.2 μm or more, and further preferably 0.3 μm or more. In addition, it is preferably 20 μm or less, more preferably 10 μm or less. In addition, the average fiber length of CNT in the CNT dispersion can be calculated as follows: the following sample is observed using a scanning electron microscope, that is, a solution obtained by diluting the CNT dispersion 50 times using a non-aqueous dispersion medium such as NMP is added dropwise to a substrate and dried, and in the observation photograph, 300 CNTs are selected at random, and the fiber lengths of each are measured and averaged. Here, in the case where the dispersion state of CNT is unstable, by diluting the CNT dispersion using a non-aqueous dispersion medium, it is easy to cause dispersion shock and produce agglomerates, so that the average fiber length tends to become smaller. Due to the above reasons, dispersion stability can be evaluated according to the average fiber length of CNT in the CNT dispersion.
[0211] Relative to the total amount of the CNT dispersion, the content of CNT in the CNT dispersion is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and further preferably 1% by mass or more. In addition, it is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less, and further preferably 8% by mass or less. By setting it to the range, CNT can be well and stably present. More preferably, it is 0.1% by mass or more and 20% by mass or less, and further preferably 0.5% by mass or more and 10% by mass or less.
[0212] In the CNT dispersion, the mass ratio of the dispersant to the CNT (dispersant / CNT) is preferably 0.01 or more, more preferably 0.05 or more, and more preferably 0.1 or more. In addition, it is preferably 1.5 or less, more preferably 1 or less, and more preferably 0.5 or less, and particularly preferably 0.40 or less. By setting it to the range, the dispersion stability of CNT can be further improved. It is more preferably 0.01 or more and 1.5 or less, and more preferably 0.1 or more and 1 or less.
[0213] The Zr content in the CNT dispersion is preferably 0.01ppm or more, more preferably 0.1ppm or more, and more preferably 1ppm or more. In addition, it is preferably 300 or less, more preferably 150ppm or less, and more preferably 100ppm or less, and particularly preferably 50ppm or less. By setting it to the range, the dispersion stability of the CNT in the CNT dispersion can be further improved. It is more preferably 0.01ppm or more and 300ppm or less, and more preferably 0.1ppm or more and 100ppm or less.
[0214] The CNT in the CNT dispersion liquid functions as a conductive material. The CNT dispersion liquid may also contain conductive materials other than CNT. As other conductive materials, for example, carbon materials such as carbon black, graphene, multilayer graphene, and graphite can be cited. In the case of using conductive materials other than CNT, from the perspective of the adsorption performance of the dispersant, carbon black is preferably used, for example, carbon black such as acetylene black, furnace black, and Ketjen black can be cited. These carbon blacks can be any one of neutral, acidic, and alkaline, and oxidized carbon black or black lead treated carbon black can also be used.
[0215] Regarding the CNT dispersion, two or more CNTs with different average outer diameters can also be prepared separately and added to the dispersion medium for preparation. As CNTs, when two or more CNTs with different average outer diameters are used, the average outer diameter of the first CNT is preferably 0.5 nm or more and less than 5 nm. The average outer diameter of the second CNT is preferably 1 nm or more and 20 nm or less. For example, a single-layer CNT can be used as the first CNT, and a multilayer CNT can be used as the second CNT. As CNTs, when two or more CNTs with different average outer diameters are used, the mass ratio of the first CNT to the second CNT is preferably 1:50 to 50:1, more preferably 1:10 to 10:1, and further preferably 1:5 to 5:1. By setting the mass ratio of the first CNT to the second CNT to the range, the mutual entanglement of the CNTs can be suppressed, thereby obtaining a dispersion with excellent fluidity.
[0216] <<Carbon nanotube resin composition>>
[0217] The carbon nanotube resin composition of this embodiment may include the carbon nanotube dispersion and a binder resin. The details of the carbon nanotube dispersion are as described above. That is, the carbon nanotube resin composition may include carbon nanotubes, a dispersant, a non-aqueous dispersion medium, and a binder resin. The carbon nanotube resin composition may further include any component. The details are as described above. The carbon nanotube resin composition can be used as a resin composition for a secondary battery.
[0218] Binder resins are generally not particularly limited as long as they can be used as binder resins for coatings, and can be appropriately selected according to the purpose. Binder resins can be resins that bind active materials, CNTs, other conductive materials, and other substances. Binder resins include, for example: homopolymers or copolymers containing ethylene, propylene, vinyl chloride, vinyl acetate, vinyl alcohol, maleic acid, acrylic acid, acrylates, methacrylic acid, methacrylates, acrylonitrile, styrene, vinyl butyral, vinyl acetal, vinyl pyrrolidone, etc. as constituent units; polyurethane resins, polyester resins, phenol resins, epoxy resins, phenoxy resins, urea resins, melamine resins, alkyd resins, acrylic resins, formaldehyde resins, silicone resins, fluororesins; cellulose resins such as carboxymethyl cellulose or its salts; elastomers such as hydrogenated or non-hydrogenated styrene-butadiene rubber and fluororubber; conductive resins such as polyaniline and polyacetylene, etc. It can also be a modified product of these resins or a copolymer of these resins. Binder resins can be used alone or in combination of two or more. Among these, when used as a binder resin for the positive electrode of a secondary battery, in terms of tolerance, preferably a homopolymer or copolymer having a fluorine atom in the molecule, such as polyvinylidene fluoride, polyvinyl fluoride, polytetrafluoroethylene, etc., modified products of these, copolymers, etc. In addition, when used as a binder resin for the negative electrode of a secondary battery, preferably CMC (carboxymethylcellulose or its salt), hydrogenated or non-hydrogenated styrene-butadiene rubber, polyacrylic acid, etc., which have good adhesion.
[0219] In the CNT resin composition, the binder resin is contained in an amount of preferably 0.5% by mass to 30% by mass, and more preferably 0.5% by mass to 25% by mass, based on the total amount of nonvolatile components of the CNT resin composition.
[0220] The CNT resin composition is preferably obtained by adding a binder resin to a CNT dispersion and mixing. The binder resin can be used in a solution (varnish) state in which the binder resin is dispersed or dissolved in a dispersion medium, but is preferably used in a state that does not include a dispersion medium, more preferably in a solid state, and particularly preferably in a powdered state. By adding a powdered binder resin to the CNT dispersion, the amount of the non-aqueous dispersion medium will not increase in the addition of the binder resin, so a CNT resin composition with a high concentration of binder resin and non-volatile components can be provided. Here, the form of the binder resin is not particularly limited, for example, it can be granular, powdery, granular, sheet-like, blocky, or short fibers.
[0221] The method of adding binder resin to CNT dispersion is not particularly limited, preferably, the binder resin is added while stirring the CNT dispersion using a stirring device. The stirring device is not particularly limited, but generally a disperser (stirring blade) is used. As its shape, there are various types such as propeller type and turbine type, but as long as the CNT resin composition can be stirred homogeneously, it is not particularly limited. In addition, the stirring speed can be appropriately adjusted according to the size or rotation speed of the stirring blade. The stirring speed is not particularly limited as long as it is within the range allowed in the actual operation process.
[0222] <<Composite material slurry for secondary battery electrodes>>
[0223] The composite slurry of this embodiment may include the carbon nanotube dispersion, the binder resin and the active substance. The composite slurry of other embodiments may include the carbon nanotube resin composition and the active substance. The details of the carbon nanotube resin composition are as described. That is, the composite slurry may include carbon nanotubes, a dispersant, a non-aqueous dispersion medium, a binder resin, and an active substance. The composite slurry may further include any component. The details are as described. The active substance may be any one of a positive electrode active substance and a negative electrode active substance. The composite slurry may be used as a composite slurry for secondary battery electrodes, or may be any one of a positive electrode composite slurry for secondary batteries and a negative electrode composite slurry for secondary batteries.
[0224] The composite material slurry may also contain other arbitrary components as needed within the scope that does not hinder the purpose of the present invention. The arbitrary components may be added at any time before the composite material slurry is made, during mixing, after mixing, or a combination of these. The arbitrary components may be the components described in the CNT resin composition.
[0225] The active material may be a positive electrode active material or a negative electrode active material. In this specification, the positive electrode active material and the negative electrode active material are sometimes referred to as "active material". The so-called active material is a material that serves as the basis of the battery reaction, and is roughly divided into positive electrode active materials and negative electrode active materials according to the electromotive force. In order to improve uniformity and processability, the composite material slurry is preferably in a slurry state.
[0226] <Positive electrode active material>
[0227] The positive electrode active material is not particularly limited, and for example, metal compounds such as metal oxides and metal sulfides that can be reversibly doped or embedded with lithium ions can be used. Examples include lithium manganese composite oxides (e.g., Li x Mn2O4 or Li x MnO2), lithium nickel composite oxides (such as Li x NiO2), lithium cobalt composite oxide (Li x CoO2), lithium nickel cobalt composite oxide (such as Li xNi 1-y Co y O2), lithium manganese cobalt composite oxide (such as Li x Mn y Co 1-y O2), lithium nickel manganese cobalt composite oxide (such as Li x Ni y Co z Mn 1-y-z O2), spinel lithium manganese nickel composite oxide (such as Li x Mn 2-y Ni y O4) and other lithium and transition metal composite oxide powders, lithium phosphorus oxide powders with olivine structure (such as Li x FePO4、Li x Fe 1-y Mn y PO4、Li x CoPO4, etc.), manganese oxide, iron oxide, copper oxide, nickel oxide, vanadium oxide (such as V2O5, V6O 13 ), transition metal oxide powders such as titanium oxide, transition metal sulfide powders such as iron sulfate (Fe2(SO4)3), TiS2, and FeS, etc. Among them, x, y, z are quantities, 0<x<1, 0<y<1, 0<z<1, 0<y+z<1. These positive electrode active materials can also be used alone or in combination. Among these active materials, active materials containing Ni and / or Mn in particular (especially when the total amount of Ni and / or Mn in the transition metal is 50 mol% or more) tend to become more alkaline due to the dissolution of components derived from the raw materials or metal ions. Due to this influence, the gelation of the binder resin or the deterioration of the dispersion state is easily caused. Therefore, in the case of batteries containing active materials containing Ni and / or Mn, this embodiment is particularly effective.
[0228] <Negative electrode active material>
[0229] The negative electrode active material is not particularly limited, and for example, metal Li, or its alloys, tin alloys, silicon alloy negative electrodes, Li x TiO2、Li x Fe2O3、Li x Fe3O4、Li x Metal oxides such as WO2, conductive polymers such as polyacetylene and polyphenylene, artificial graphite such as high-graphite carbon materials, or carbonaceous powders such as natural graphite, and resin-fired carbon materials.
[0230] Here, x is the number, 0<x<1. These negative electrode active materials can also be used alone or in combination. In particular, when a silicon alloy negative electrode is used, the theoretical capacity is large, but the volume expansion is extremely large. Therefore, it is preferably used in combination with artificial black lead such as a highly black lead carbon material, or carbonaceous powder such as natural black lead, resin fired carbon material, etc.
[0231] Based on the mass of the active material (the mass of the active material is set to 100 mass %), the content of CNT in the composite material slurry is preferably 0.01 mass % or more, more preferably 0.03 mass % or more, and more preferably 0.05 mass % or more. In addition, preferably 10 mass % or less, more preferably 5 mass % or less, and more preferably 3 mass % or less. If it exceeds the range, the filling amount of the active material in the electrode is reduced and the battery is reduced. In addition, if it is less than the range, the conductivity of the electrode and the battery sometimes becomes insufficient.
[0232] The content of the dispersant in the composite material slurry is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, based on the mass of the active material (the mass of the active material is set to 100% by mass), and preferably 10% by mass or less, more preferably 5% by mass or less.
[0233] Based on the mass of the active material (the mass of the active material is set to 100 mass%), the content of the binder resin in the composite material slurry is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and preferably 20 mass% or less, more preferably 10 mass% or less.
[0234] Based on the mass of the composite slurry (the mass of the composite slurry is set to 100 mass%), the nonvolatile content in the composite slurry is preferably 40 mass% or more, more preferably 50 mass% or more, and preferably 90 mass% or less, more preferably 85 mass% or less.
[0235] As a method for preparing a composite material slurry, it is preferred to further add an active substance to the CNT resin composition and stir it. The stirring device used in the stirring is not particularly limited. The stirring device can use a disperser, a homogenizer, etc.
[0236] In addition, the composite slurry may further include carbon black, which functions as a conductive material. Carbon black is preferably included in the composite slurry within the range that does not damage the effect of the present invention, and CNT is preferably 1% to 80% by mass, more preferably 1% to 50% by mass, relative to the total amount of the conductive material containing carbon black and CNT. Within these ranges, the dispersion state of CNT can be controlled, and high dispersibility and fluidity can be better maintained in the state containing the binder resin. Furthermore, relative to the total mass of the composite slurry, carbon black is preferably 10% by mass or less, more preferably 5% by mass or less. In addition, the method for manufacturing the composite slurry includes a process for adding an active substance to the CNT resin composition, but may be included in the addition of active substances to the CNT resin composition before, after, at the same time, or in a combination of these, further adding carbon black. Alternatively, an active substance may be added to a CNT resin composition containing carbon black in advance, or an active substance and carbon black may be further added to a CNT resin composition containing carbon black in advance.
[0237] <<Electrode film>>
[0238] The electrode film of the present embodiment is a coating film formed by the composite material slurry. That is, the electrode film may include CNT, a dispersant, a binder resin, and an active material. The active material may be any one of a positive electrode active material and a negative electrode active material. The electrode film may also include any component. The details are as described. The electrode film can be used as an electrode film for a secondary battery electrode, or it can be any one of an electrode film for a secondary battery positive electrode and an electrode film for a secondary battery negative electrode. The electrode film may be a coating film obtained using the composite material slurry, for example, it can be formed by applying the composite material slurry and drying it. The electrode film can be used to provide an electrode. The electrode may include a collector and an electrode film. The composite material slurry can be applied to the collector and dried to form a coating film to obtain an electrode. The positive electrode can be provided using an electrode film containing a positive electrode active material, and the negative electrode can be provided using an electrode film containing a negative electrode active material. These positive electrodes and negative electrodes can be provided as the positive electrode and negative electrode of the secondary battery, respectively.
[0239] The material or shape of the current collector is not particularly limited, and the material or shape suitable for various secondary batteries can be appropriately selected. For example, as the material of the current collector, metals or alloys such as aluminum, copper, nickel, titanium, or stainless steel can be listed. In addition, as the shape, a foil on a flat plate can generally be used, but a current collector with a roughened surface, a perforated foil-shaped current collector, and a mesh-shaped current collector can also be used. The thickness of the current collector is preferably about 0.5 μm to 30 μm.
[0240] As a method for applying the composite material slurry on the collector, there is no particular restriction, and known methods can be used. Specifically, it can be listed as: die coating, dip coating, roller coating, blade coating, spray coating, gravure coating, screen printing or electrostatic coating, etc. As a drying method after coating, it can be placed to dry, air dryer, warm air dryer, infrared heater, far infrared heater, etc., but it is not particularly limited to these. In addition, after the coating of the composite material slurry, it can also be rolled using a lithographic press, a calender roller, etc. The thickness of the electrode film is, for example, more than 1 μm and less than 500 μm, preferably more than 10 μm and less than 300 μm.
[0241] <<Secondary battery>>
[0242] The secondary battery of this embodiment includes a positive electrode, a negative electrode, and an electrolyte, and at least one of the positive electrode and the negative electrode includes the electrode film. The positive electrode and the negative electrode may include a current collector and an electrode film, respectively. The details are as described above. The secondary battery is more preferably a lithium ion secondary battery.
[0243] As the positive electrode, a positive electrode in which an electrode film is produced by coating a composite material slurry containing a positive electrode active material on a current collector and drying the composite material slurry can be used. As the negative electrode, a negative electrode in which an electrode film is produced by coating a composite material slurry containing a negative electrode active material on a current collector and drying the composite material slurry can be used. The positive electrode active material and the negative electrode active material can use the above-mentioned substances. The composite material slurry can be produced according to the above-mentioned method.
[0244] The electrolyte may be any of a liquid electrolyte, a gel electrolyte, and a solid electrolyte. For example, the liquid electrolyte may contain an electrolyte salt such as a lithium salt and a non-aqueous dispersion medium.
[0245] As the electrolyte salt, various known electrolyte salts in which ions can move can be used. For example, lithium salts such as LiBF4, LiClO4, LiPF6, LiAsF6, LiSbF6, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, Li(CF3SO2)3C, LiI, LiBr, LiCl, LiAlCl, LiHF2, LiSCN, or LiBPh4 (wherein Ph is phenyl) can be cited, but are not limited to these. The electrolyte salt is preferably dissolved in a non-aqueous dispersion medium and used as an electrolyte.
[0246] The non-aqueous dispersion medium is not particularly limited, and examples thereof include carbonates such as ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate; lactones such as γ-butyrolactone, γ-valerolactone, and γ-octalactone; glycol dimethyl ethers (glymes) such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-methoxyethane, 1,2-ethoxyethane, and 1,2-dibutoxyethane; esters such as methyl formate, methyl acetate, and methyl propionate; sulfoxides such as dimethyl sulfoxide and cyclopentane; and nitriles such as acetonitrile, etc. These solvents may be used alone, or two or more thereof may be mixed and used.
[0247] The secondary battery preferably includes a separator. Examples of the separator include polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and nonwoven fabrics subjected to hydrophilic treatment. However, the separator is not limited to these.
[0248] The structure of the secondary battery is not particularly limited, and generally includes a positive electrode, a negative electrode, and a separator provided as required, and can be made into various shapes according to the purpose of use, such as paper-shaped, cylindrical, button-shaped, and laminated.
[0249] [Example]
[0250] The present invention will be described in more detail below with reference to the following examples. The present invention is not limited to the following examples unless otherwise specified. In addition, "parts" means "parts by mass" and "%" means "% by mass" unless otherwise specified.
[0251] In the examples and comparative examples, the following CNTs were used.
[0252] BT1003M: LUCAN BT1003M, manufactured by LG Chem Ltd., multi-layer CNT, outer diameter 10nm~15nm
[0253] JENOTUBE 10B: Made by JEIO, multi-layer CNT, outer diameter 7nm to 12nm
[0254] In Examples and Comparative Examples, the following dispersants were used.
[0255] H-NBR1: Therban (R) AT 3404 (manufactured by ARLANXEO, hydrogenated acrylonitrile-butadiene rubber)
[0256] H-NBR2: Zetpole 2000L (manufactured by Japan Zeon, hydrogenated acrylonitrile-butadiene rubber)
[0257] ·PVB: BL-10 (manufactured by Sekisui Chemical Industry, polyvinyl butyral)
[0258] ·PVP: K-30 (made by ISP, polyvinyl pyrrolidone)
[0259] ·PVA: Kuraray Poval 3-86SD (manufactured by Kuraray, modified polyvinyl alcohol)
[0260] In Examples and Comparative Examples, the following binder resins were used.
[0261] PVDF: KF Polymer W#7300 (manufactured by Kureha, polyvinylidene fluoride resin)
[0262] PTFE: PTFED-210C (Daikin Industrial Manufacturing, polytetrafluoroethylene)
[0263] <CNT>
[0264] Table 1 shows the types of CNTs and production conditions. In the example of dry pulverization, the endpoint index of the CNT treatment was set to a bulk density of 0.045 g / cm 3 ~0.125g / cm 3 The Zr content is within the range of 3ppm to 500ppm.
[0265] (Example 1: CNT1)
[0266] In a 60L dynamic mill, 8mm diameter zirconium oxide beads were loaded as a grinding medium at a filling rate of 70%, 100kg of BT1003M as a raw material CNT was supplied at a flow rate of 120kg / h±20kg / h (hour), and the mill was processed by a circulation grinding method at a peripheral speed of 4m / s (second) for 2 hours to obtain CNT1. The sample was taken out and the volume density was confirmed to be 0.062g / cm 3 , Zr content is 6ppm, bulk density and Zr content are both within the specified range, and the treatment process is completed. In the treatment process, cooling water (10°C) is flowed to the vessel (flow rate 10L / min) to cool the powder at the outlet to 45°C±10°C.
[0267] (Examples 2 to 9: CNT2 to CNT9)
[0268] According to the raw material CNT, processing time, processing flow rate, and dry dispersion method described in Table 1, CNT dry pulverization was performed in the same manner as in Example 1 to obtain CNT2 to CNT9. In each treatment step, cooling water (10°C) was flowed to the vessel (flow rate 10 L / min) to cool the outlet powder to 45°C ± 10°C.
[0269] (Comparative Example 1: Comparison with CNT1)
[0270] BT1003M which was not subjected to the pulverization process and was in an unprocessed state was set as comparison CNT1.
[0271] (Comparative Example 2: Comparison CNT2)
[0272] In a 60L dynamic mill, 8mm diameter zirconium oxide beads were loaded as a grinding medium at a filling rate of 70%, 100kg of BT1003M as a raw material CNT was supplied at a flow rate of 120kg / h±20kg / h, and the raw material CNT was processed for 15 hours by a circulating grinding method at a peripheral speed of 4m / s to obtain comparative CNT2. During the processing step, cooling water (10°C) was flowed to the vessel (flow rate 10L / min) for cooling so that the outlet powder temperature was 45°C±10°C.
[0273] (Comparative Example 3: Comparison with CNT3)
[0274] In a 60L dynamic mill, zirconia beads with a diameter of 8mm as a grinding medium were loaded at a filling rate of 70%, 100kg of BT1003M as a raw material CNT was supplied at a flow rate of 120kg / h±20kg / h, and the raw material CNT was processed by a circulating grinding method at a peripheral speed of 4m / s for 15 hours to obtain comparative CNT3. During the grinding process, normal temperature water was allowed to flow to the vessel to prevent device failure caused by temperature rise.
[0275] (Comparative Example 4: Comparative CNT4)
[0276] In a ball mill with a capacity of 250L, zirconia beads with a diameter of 20mm were loaded as a grinding medium at a filling rate of 35%, and 5kg of BT1003M as raw CNT was loaded. The ball mill was processed by batch grinding at a peripheral speed of 10m / s for 20 hours to obtain comparative CNT4.
[0277] (Comparative Example 5: Comparison with CNT5)
[0278] In a 150L mill, 8mm diameter zirconium oxide beads were charged as a grinding medium at a filling rate of 70%, and 3kg of BT1003M CNT as a raw material was charged and the mill was rotated at a speed of 150min. -1Comparative CNT5 was obtained by batch pulverization for 10 hours.
[0279] <<CNT physical properties and evaluation>>
[0280] The physical properties of CNT were measured and evaluated by the following methods. The obtained results are shown in Table 1.
[0281] <<Zr content>>
[0282] The Zr content of CNTs was measured according to the following procedure.
[0283] First, 0.1 g ± 0.02 g of CNT was placed in a small glass bottle for decomposition, and nitric acid was added, and the decomposition was performed using a microwave sample decomposition device. The product was added to the decomposition liquid, adjusted to 25 ml, filtered using a membrane filter, and the filtrate was analyzed using an ICP analyzer to determine the Zr content (ppm).
[0284] <Volume density X of CNT>
[0285] The bulk density is measured according to the following procedure in accordance with Japanese Industrial Standards (JIS) K 5101-12-1.
[0286] First, before the measurement, the CNTs were vacuum dried and pretreated at a pretreatment temperature of 305°C and a pretreatment time of 18 to 21 hours. Next, in order to break up the agglomerates formed by the CNT powder during storage and allow the obtained sample to flow freely into the measurement container until it overflows, a sufficient amount of sample for the test was prepared through a 0.5 mm sieve. The prepared CNT powder was allowed to fall freely and contained in a 30 ml stainless steel cylindrical container. After the raised portion of the upper surface of the container was scraped flat, the mass of the CNT powder was calculated and divided by the volume of the container to calculate the volume density (g / cm 3 ).
[0287] <Maximum solvent absorption capacity Y of CNT>
[0288] The maximum solvent absorption capacity Y is the maximum mass of the solvent absorbed by the CNT per unit mass of the CNT when the CNT absorbs the solvent. The maximum mass of the solvent absorbed by the CNT is the total mass of the solvent added until the solvent flows out of the CNT powder when the solvent is added dropwise to the CNT powder. The maximum solvent absorption capacity Y is measured according to the following process.
[0289] First, before the measurement, the CNT was vacuum dried at a pretreatment temperature of 305°C and a pretreatment time of 18 to 21 hours for pretreatment. Next, 5 g (V (g)) of CNT powder was placed in a cylindrical polypropylene container with a diameter of 10 cm by natural fall at 25°C. In a static state, N-methyl-2-pyrrolidone was dripped onto the surface of the CNT powder at a rate of 0.5 g per time and at intervals of 1 minute. The total mass (W (g)) of N-methyl-2-pyrrolidone dripped until the liquid of N-methyl-2-pyrrolidone was not absorbed by the CNT powder and began to flow out to the surface of the CNT powder was measured. The maximum solvent absorption capacity was calculated according to the following formula (5).
[0290] Y=W / V···Formula (5)
[0291] (In formula (5), V is the mass of CNT, and W is the maximum mass of N-methyl-2-pyrrolidone that is added dropwise to CNT of V (g) and absorbed by CNT at 25°C)
[0292] <CNT powder resistivity>
[0293] Using a powder resistivity measuring device (Nittoseiko Analytech Co., Ltd.: Loresta GP Powder Resistivity Measuring System MCP-PD-51), the sample mass was set to 0.8 g, and a powder probe unit (four-probe-ring electrode, electrode spacing 5.0 mm, electrode radius 1.0 mm, sample radius 12.5 mm) was used. The applied voltage limiter was set to 90 V to measure the volume resistivity [Ω·cm] of the conductive powder under various pressures. For 1 g / cm 3 The value of the CNT powder resistivity at a density of 1.5 Å was evaluated.
[0294] [Table 1-1]
[0295] Table 1-1
[0296]
[0297] [Table 1-2]
[0298] Table 1-2
[0299]
[0300] [Table 1-3]
[0301] Table 1-3
[0302]
[0303] In Table 1, the bulk density change rate is a value obtained by the following formula based on the bulk density X after dry pulverization and the bulk density X' before dry pulverization, and the powder resistance value change rate is a value obtained by the following formula based on the powder resistance value Re after dry pulverization and the powder resistance value Re' before dry pulverization.
[0304] Volume density change rate (%) = (X / X'-1) × 100
[0305] Powder resistance change rate (%) = (Re / Re'-1) × 100
[0306] <CNT dispersion>
[0307] (Example 1-1)
[0308] According to the materials and compositions shown in Table 2, materials were added in order to prepare a CNT dispersion as follows.
[0309] First, NMP is placed in a stainless steel jacketed tank and heated to 50°C. After adding a dispersant (H-NBR1) and an additive (NaOH) while stirring with a disperser, stir for 1 hour to dissolve the dispersant (H-NBR1). Then, 25 parts by mass of CNT are added relative to 100 parts by mass of CNT (CNT1) while stirring with a disperser, and a square hole high shear screen is installed on a high shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion is performed at a speed of 8,000 rpm for 5 minutes. By repeating the CNT addition and dispersion process four times, all CNTs are added, and batch dispersion is performed using a high shear mixer until the whole becomes uniform and the dispersed particle size is made less than 250 μm using a particle size meter (grind gauge) with a maximum depth of 300 μm in the groove. Then, the tank with a jacket is supplied to the bead mill (SC100, manufactured by Nippon Coke) via a pipe, and the dispersed liquid is retained for 5 minutes under the conditions of a bead diameter of 1.25 mm, a bead filling rate of 60%, a peripheral speed of 10 m / s, and a supply speed of 800 g / min, and is dispersed by a circulation method. Furthermore, the pipe is switched and the dispersed liquid is supplied to a high-pressure homogenizer (Star Burst Labo HJP-17007, manufactured by SUGINO MACHINE) for a circulation method. The dispersion process is carried out using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. After the dispersion was dispersed until the viscosity of the dispersion at 60 rpm measured by a B-type viscometer (TOKI SANGYO, VISCOMETER, Model: BL) was 3,000 mPa·s or less, the dispersion was treated 15 times with a high pressure homogenizer to obtain a CNT dispersion 1.
[0310] (Examples 1-2~1-14)
[0311] Except for changing the materials and compositions shown in Table 2, CNT dispersions 2 to 13 were obtained in the same manner as in Example 1-1.
[0312] (Example 1-15)
[0313] According to the materials and compositions shown in Table 2, materials were added in order to prepare a CNT dispersion as follows.
[0314] First, NMP is placed in a stainless steel jacketed tank and heated to 50°C. After adding the dispersant (H-NBR1) and the additive (NaOH) while stirring with a disperser, stir for 1 hour to dissolve the dispersant (H-NBR1). Then, while stirring with a disperser, 25 parts by mass of CNT are added relative to 100 parts by mass of CNT (CNT1), and a square hole high shear screen is installed on a high shear mixer (L5M-A, manufactured by SILVERSON), and batch dispersion is performed at a speed of 8,000 rpm for 5 minutes. By repeating the CNT addition and dispersion process four times, all CNTs are added, and batch dispersion is performed using a high shear mixer until the whole becomes uniform and the dispersed particle size is made less than 250 μm using a particle size meter with a maximum depth of 300 μm in the groove. Then, the tank with a jacket is supplied to the bead mill (SC100, manufactured by Nippon Coke) via a pipe, and the dispersed liquid is retained for 10 minutes under the conditions of a bead diameter of 1.25 mm, a bead filling rate of 60%, a peripheral speed of 10 m / s, and a supply speed of 800 g / min, and is dispersed by a circulation method. Furthermore, the pipe is switched and the dispersed liquid is supplied to a high-pressure homogenizer (Star Burst Labo HJP-17007, manufactured by SUGINO MACHINE) for a circulation method. The dispersion process is carried out using a single nozzle chamber with a nozzle diameter of 0.25 mm and a pressure of 100 MPa. After the dispersion had a viscosity of 3,000 mPa·s or less at 60 rpm as measured by a B-type viscometer (TOKI SANGYO, VISCOMETER, MODEL: BL), the dispersion was treated 15 times with a high-pressure homogenizer to obtain a CNT dispersion 15.
[0315] (Comparative Examples 1-1 to 1-5)
[0316] Comparative CNT dispersions 1 to 5 were obtained in the same manner as in Example 1-1 except that the materials and compositions shown in Table 2 were changed.
[0317] In addition, the additives and acids described in Table 2 are as follows.
[0318] NaOH: Sodium hydroxide (produced by Tokyo Chemical Industry, purity > 98.0%, granular)
[0319] ·Aminoethanol: 2-aminoethanol (manufactured by Tokyo Chemical Industry, purity > 99.0%)
[0320] <<Measurement and evaluation of physical properties of CNT dispersion>>
[0321] The physical properties of the CNT dispersion were measured and evaluated by the following methods. The obtained results are shown in Tables 2 and 3.
[0322] (Shear viscosity of CNT dispersion)
[0323] The cutting speed of CNT dispersion is 1.0s -1 The viscosity at 25°C was evaluated by using a rheometer (RheoStress 1 rotational rheometer manufactured by Thermo Fisher Scientific, Inc.) with a cone of 60 mm in diameter and 2° at a shear rate of 0.01 s -1 ~1000s -1 The flow curve measurement is performed in the range of . The shear rate over time is evaluated by performing the flow curve measurement on the CNT dispersion in a static state with the liquid temperature adjusted to 25°C.
[0324] (Complex elastic modulus of CNT dispersion)
[0325] The complex elastic modulus of the CNT dispersion was evaluated by using a rheometer (RheoStress 1 rotational rheometer manufactured by Thermo Fisher Scientific Co., Ltd.) with a diameter of 60 mm and a 2° cone, and performing dynamic viscoelasticity measurement at a strain rate of 0.01% to 5% at 25°C and a frequency of 1 Hz. The shear rate over time was evaluated by performing the dynamic viscoelasticity measurement on the CNT dispersion in a static state with the liquid temperature adjusted to 25°C.
[0326] Table 3 shows the measurement results of the shear viscosity η (Pa·s) and the complex elastic modulus G* (Pa) measured using the CNT dispersions of Examples 1-2, 1-8, and Comparative Example 1-3.
[0327] In Table 4, the regression line expressed by the least square method was calculated from the scatter plot of the natural logarithm (ln(η)) of the shear viscosity η (Pa·s) and the complex elastic modulus G* (Pa) of the measurement results of Examples 1-2, 1-8, and Comparative Example 1-3, and the coefficient of determination R was calculated. 2 , slope a, y slice b.
[0328] Figure 1 In FIG. 1 , there is shown as an example a scattergram in which the results obtained by measuring the CNT dispersions of Examples 1-2 and 1-8 and Comparative Example 1-3 using the CNT dispersions after being stored at 40° C. for 1 day, 7 days, and 14 days are plotted.
[0329] For example, the coefficient of determination R obtained from the regression line of the CNT dispersion of Example 1-2 is 2 is 1.00, the slope a is 8.4, the y slice b is 4.1, and the determination coefficient R obtained from the regression line of the CNT dispersion of Comparative Example 1-3 2 is 0.79, the slope a is 20.8, and the y slice b is -0.5.
[0330] The judgment criteria in Table 4 are as follows.
[0331] [Determination coefficient R 2 Criteria for determination]
[0332] A: 0.95 or more
[0333] B: 0.90 or more but less than 0.95
[0334] C: 0.85 or more and less than 0.90
[0335] D: less than 0.85
[0336] [Criteria for determining the slope a]
[0337] A: 7 or above and under 14
[0338] B: 5 or more but less than 7, or 14 or more but less than 15
[0339] C: 2 or more but less than 5, or 15 or more but less than 20
[0340] D: Under 2, or over 20
[0341] [Judgment criteria for y slice b]
[0342] A: 0 or more and less than 6
[0343] B: -3 or more and less than 0, or 6 or more and less than 8
[0344] C: -5 or more but less than -3, or 8 or more but less than 10
[0345] D: less than -5, or more than 10
[0346] (Filtration speed)
[0347] The dispersibility of the CNT dispersion was evaluated by the filtration rate.
[0348] The method of the filtration speed test is to add 80g of NMP to 40g of CNT dispersion and shake the hand to mix it fully. By putting all of them into a 300mL filter holder for vacuum filtration, the amount is placed under the receiving container in the suction filter bell, and the weight relative to the time of passing through a 10μm mesh is measured. The shorter the time for filtering all the diluted CNT dispersion, the better the dispersibility. In addition, the poorly dispersed dispersion has condensed CNTs and cannot be filtered completely. If the evaluation benchmark is + or above, it can be practical.
[0349] [Evaluation criteria]
[0350] +++: Less than 30 seconds
[0351] ++: 30 seconds or more and less than 100 seconds
[0352] +: more than 100 seconds
[0353] NG: Unable to filter all
[0354] (Acid stability)
[0355] The fluidity and dispersion stability of the CNT dispersion were evaluated by acid stability.
[0356] Regarding the evaluation of acid stability, 5 parts by mass of succinic acid (succinic acid: manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., purity >99.5%) were added to 100 parts by mass of the CNT dispersion, and the initial viscosity of the CNT dispersion containing the acid and the viscosity of the CNT dispersion containing the acid after being allowed to stand and stored at 40°C for 7 days were measured respectively. The change rate of the viscosity after standing and storing at 40°C for 7 days relative to the initial viscosity was calculated and evaluated.
[0357] The change rate of viscosity is expressed as a percentage of the viscosity value after standing and storing at 40°C for 7 days divided by the initial viscosity value. The viscosity of the CNT dispersion is measured using a B-type viscometer ("BL" manufactured by Toki Sangyo) at a temperature of 25°C, after being fully stirred with a spatula, and then immediately at a B-type viscometer rotor rotation speed of 60 rpm. The smaller the change rate, the better. If the evaluation standard is + or above, it can be practical.
[0358] [Evaluation criteria]
[0359] +++: less than 200%
[0360] ++: 200% or more and less than 500%
[0361] +: 500% or more but less than 1000%
[0362] NG: 1000% or more (gelation)
[0363] [Table 2]
[0364] Table 2
[0365]
[0366] [Table 3]
[0367] Table 3
[0368]
[0369] [Table 4-1]
[0370] Table 4-1
[0371]
[0372] [Table 4-2]
[0373] Table 4-2.
[0374]
[0375] [Table 4-3]
[0376] Table 4-3.
[0377]
[0378] <Manufacturing of carbon nanotube resin composition, positive electrode composite material slurry and positive electrode>
[0379] (Examples 2-1 to 2-19, Comparative Examples 2-1 to 2-5)
[0380] According to the combination and composition ratio shown in Table 5, a carbon nanotube resin composition, a positive electrode composite material slurry and a positive electrode were prepared in the following manner.
[0381] The CNT dispersion was added to a stainless steel jacketed tank, and the temperature of the jacketed tank was heated to 60°C so that the liquid temperature measured by a thermocouple thermometer was 60°C. All the binder resin was added at a rate of 0.8 parts by mass / minute while stirring with a disperser. The temperature was adjusted so that the liquid temperature measured by the thermocouple thermometer was maintained at 60°C, and the disperser was used for stirring for 3 hours to dissolve all the binder resin, thereby obtaining a carbon nanotube resin composition.
[0382] Capacity 150cm 3 The CNT resin composition and the positive electrode active material were added to a plastic container, and stirred at 2,000 rpm for 5 minutes using a rotation / revolution mixer (manufactured by Thinky, defoaming stirring Taro, ARE-310) to obtain a positive electrode composite material slurry. The non-volatile component of the positive electrode composite material slurry was set to 78% by mass.
[0383] After applying the positive electrode composite material slurry onto an aluminum foil with a thickness of 20 μm using an applicator, the electrode film was heated and dried in an electric oven at 120°C ± 5°C for 25 minutes to produce an electrode film. Afterwards, the electrode film was rolled using a roller press (manufactured by Thank-Metal, 3t hydraulic roller press) to obtain a positive electrode (positive electrode 1 to positive electrode 18, comparison positive electrode 1 to comparison positive electrode 4). In addition, the unit area weight of each unit of the composite material layer is 20 mg / cm 2 The density of the composite material layer after calendering is 3.2g / cm 3 .
[0384] In the examples and comparative examples, the following positive electrode active materials were used.
[0385] NMC1: Cellseed NMC (LiNi 0.6 Co 0.2 Mn 0.2 O2, manufactured by Nippon Chemical Industry)
[0386] NMC2: S800(LiNi 0.8 Mn 0.1 Co 0.1 O2, manufactured by Jinhe)
[0387] NCA: NAT-7050(LiNi 0.8 Co 0.15 Al 0.05 O2, BASF Toda Battery Materials Manufacturing)
[0388] LFP: HED (trademark) LFP-400 (lithium iron phosphate, manufactured by BASF)
[0389] <Evaluation of positive electrode>
[0390] (Conductivity of positive electrode)
[0391] For the obtained positive electrode, the surface resistivity (Ω / Y) of the composite material layer was measured using Loresta GP, MCP-T610 manufactured by Mitsubishi Chemical Analysis Technology. After the measurement, the volume resistivity (Ω·cm) of the positive electrode was multiplied by the thickness of the composite material layer. The thickness of the composite material layer was measured using a film thickness meter (NIKON, DIGIMICRO MH-15M), and the average value obtained by measuring 3 points in the electrode was subtracted from the thickness of the aluminum foil to obtain the volume resistivity (Ω·cm) of the positive electrode. The smaller the volume resistivity, the better.
[0392] [Evaluation criteria]
[0393] ++++: less than 10Ω·cm
[0394] +++: 10 Ω·cm or more and less than 20 Ω·cm
[0395] ++: 20Ω·cm or more and less than 30Ω·cm
[0396] +: 30Ω·cm or more
[0397] (Adhesion of positive electrode)
[0398] The obtained positive electrode is cut into two rectangles of 90mm×20mm with the coating direction as the long axis. The peel strength is measured using a desktop tensile tester (Strograph E3 manufactured by Toyo Seiki Seisaku-sho), and the evaluation is performed by a 180-degree peel test method. Specifically, a double-sided tape (No.5000NS, manufactured by Nitoms) of 100mm×30mm size is attached to a stainless steel plate, so that the composite material layer side of the prepared positive electrode is in close contact with the other side of the double-sided tape, and a test sample is set. Then, the test sample is fixed vertically in a manner such that the short sides of the rectangle are located above and below, and the end of the aluminum foil is pulled from the bottom to the top at a certain speed (50mm / minute) while being peeled off, and the average value of the stress at this time is set as the peel strength. The higher the peel strength, the better.
[0399] [Evaluation criteria]
[0400] ++++: 0.8N / cm or more
[0401] +++: 0.5 N / cm or more and less than 0.8 N / cm
[0402] ++: 0.3N / cm or more and less than 0.5N / cm
[0403] +: less than 0.3N / cm
[0404] [Table 5]
[0405] Table 5
[0406]
[0407] <Manufacturing of secondary batteries>
[0408] (Production of standard negative electrode)
[0409] In a 150 ml plastic container, 0.5 parts of acetylene black (DENKA BLACK (registered trademark) HS-100, manufactured by DENKA), 1 part of MAC500LC (carboxymethylcellulose sodium salt Sunrose special type MAC500L, manufactured by Nippon Paper, non-volatile matter 100%), and 98.4 parts of water were added, and stirred at 2,000 rpm for 30 seconds using a rotation / revolution mixer (Defoaming Stirring Taro, manufactured by Thinky, ARE-310). Furthermore, 97 parts by mass of artificial graphite (CGB-20, manufactured by Nippon Graphite Industry) as an active material was added, and stirred at 2,000 rpm for 150 seconds using a rotation / revolution mixer (Defoaming Stirring Taro, manufactured by Thinky, ARE-310). Then, 3.1 parts of SBR (styrene butadiene rubber) (styrene butadiene rubber, TRD2001, non-volatile content 48%, manufactured by JSR) was added, and the mixture was stirred at 2,000 rpm for 30 seconds using a rotation / revolution mixer (Thinky Defoaming Stirring Taro, ARE-310) to obtain a standard negative electrode composite material slurry. The non-volatile content of the standard negative electrode composite material slurry was set to 50% by mass.
[0410] The standard negative electrode composite material slurry was applied onto a copper foil with a thickness of 20 μm as a current collector using an applicator, and then dried in an electric oven at 80°C ± 5°C for 25 minutes to adjust the unit area weight per unit area of the electrode to 10 mg / cm 2 Then, the composite material layer was rolled using a roller press (manufactured by Thank-Metal, 3 t hydraulic roller press) to obtain a composite material layer with a density of 1.6 g / cm 3 The standard negative electrode.
[0411] (Examples 3-1 to 3-19, Comparative Examples 3-1 to 3-5)
[0412] The positive electrode and standard negative electrode described in Table 8 were punched into 50 mm × 45 mm and 45 mm × 40 mm, respectively. The punched positive electrode and standard negative electrode, as well as the separator (porous polypropylene film) inserted therebetween, were inserted into an aluminum laminate bag and dried in an electric oven at 70°C for 1 hour. After that, 2 mL of an electrolyte solution (a mixed solvent prepared by mixing ethylene carbonate, dimethyl carbonate and diethyl carbonate in a volume ratio of 1:1:1, and then as an additive, 1 mass part of vinylene carbonate was added to 100 mass parts, and LiPF6 was dissolved at a concentration of 1M) was injected into a glove box filled with argon gas, and then the aluminum laminate was sealed to prepare secondary batteries respectively.
[0413] <Battery Evaluation>
[0414] (Rate characteristics of secondary batteries)
[0415] The obtained secondary battery was placed in a constant temperature room at 25°C, and a charge and discharge device (manufactured by Hokuto Electric, SM-8) was used for charge and discharge measurement. After constant current and constant voltage charging (cutoff current 1mA (0.02C)) at a charge end voltage of 4.3V at a charging current of 10mA (0.2C), constant current discharge was performed at a discharge current of 10mA (0.2C) with a discharge end voltage of 3V. After repeating the above operation three times, constant current and constant voltage charging (cutoff current (1mA and 0.02C)) was performed at a charge current of 10mA (0.2C) with a charge end voltage of 4.3V, and constant current discharge was performed at a discharge current of 0.2C and a discharge current of 3C until the discharge end voltage reached 3.0V, and the discharge capacity was calculated respectively. The rate characteristic is the ratio of the 0.2C discharge capacity to the 3C discharge capacity, which can be expressed by the following formula 1.
[0416] (Formula 1) Rate characteristics = 3C discharge capacity / third 0.2C discharge capacity × 100 (%)
[0417] The higher the rate characteristic, the more ideal it is.
[0418] [Evaluation criteria]
[0419] ++++: more than 80%
[0420] +++: 60% or more and less than 80%
[0421] ++: 40% or more and less than 60%
[0422] +: Less than 40%
[0423] (Cycle characteristics of secondary batteries)
[0424] The obtained secondary battery was placed in a constant temperature room at 25°C, and a charge and discharge device (manufactured by Hokuto Electric, SM-8) was used for charge and discharge measurement. At a charging current of 25mA (0.5C), constant current and constant voltage charging was performed at a charge termination voltage of 4.3V (cut-off current 2.5mA (0.05C)), and then constant current discharge was performed at a discharge current of 25mA (0.5C) with a discharge termination voltage of 3V. The operation was repeated 200 times. The cycle characteristics are the ratio of the 3rd 0.5C discharge capacity to the 200th 0.5C discharge capacity at 25°C, which can be expressed by the following formula 2.
[0425] (Formula 2) Cycle characteristics = 200th 0.5C discharge capacity / 3rd 0.5C discharge capacity × 100 (%)
[0426] The higher the cycle characteristics, the better.
[0427] [Evaluation criteria]
[0428] ++++: more than 85%
[0429] +++: 80% or more but less than 85%
[0430] ++: 50% or more and less than 80%
[0431] +: Less than 50%
[0432] [Table 6]
[0433] Table 6
[0434]
[0435] As shown in Tables 2 to 6, it can be confirmed that the carbon nanotubes that meet the scope of the present invention show excellent conductivity and dispersibility, and the carbon nanotube dispersion containing the carbon nanotubes has excellent fluidity, high dispersion stability and storage stability. In addition, the composite material slurry for secondary battery electrodes has excellent dispersibility of CNT in a state containing active materials, and the conductivity and adhesion of the electrode film using the slurry are high. Furthermore, the rate characteristics and cycle characteristics of the obtained secondary battery are excellent. Thus, it can be confirmed that it is a secondary battery with high output, high capacity and long life.
[0436] CNT2 to CNT4 of Examples 2 to 4 and CNT6 to CNT9 of Examples 6 to 9 respectively meet the scope of the present invention, and the CNT dispersions using these have excellent filterability and acid stability, and the battery performance of secondary batteries using these is improved. CNT1 of Example 1 and CNT5 of Example 5 are reference examples.
[0437] As mentioned above, although this invention was demonstrated with reference to embodiment, this invention is not limited to this. Various changes which can be understood by a person skilled in the art can be made to the structure and detail of this invention within the scope of this invention.
[0438] The disclosure of this application is related to the subject matter described in Japanese Patent Application No. 2023-105931 filed on June 28, 2023 and the subject matter described in Japanese Patent Application No. 2024-089114 filed on May 31, 2024, and all disclosed contents are incorporated by reference in this application.
Claims
1. A carbon nanotube, wherein: The bulk density X is 0.095 g / cm 3 Above and 0.125g / cm 3 Hereinafter, the Zr content is 5 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the following formula (5) is 8.0 or more. Y=W / V···Formula (5) (In formula (5), V is the mass (g) of the carbon nanotubes, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotubes when N-methyl-2-pyrrolidone is added dropwise to the carbon nanotubes of V (g) at 25°C.) 2. The carbon nanotube according to claim 1, wherein: Bulk density X (g / cm 3 ) and the maximum solvent absorption capacity Y of the carbon nanotubes satisfy all of the following equations (1) to (4). Y≦-200X+37···Formula (1) Y≧200X-17···Formula (2) Y≧-200X+27···Formula (3) Y≦200X+7···Formula (4) 3. The carbon nanotube according to claim 1 or 2, wherein: The average fiber length is 0.2 μm or more and 1.1 μm or less.
4. The carbon nanotube according to claim 1 or 2, wherein: The average fiber length is 0.2 μm or more and 1.0 μm or less, and the Zr content is 15 ppm or more and 200 ppm or less. 5 . A carbon nanotube dispersion, comprising the carbon nanotubes according to claim 1 or 2 , a dispersant and a non-aqueous dispersion medium.
6. The carbon nanotube dispersion according to claim 5, wherein The coefficient of determination R of the regression line represented by the following formula (I) is 2 is greater than 0.85, the slope a is 2≦a<20, and the y slice b is -5≦b<10. y=ax+b ···Formula (I) (Formula (1) is a regression line obtained by the least square method from a scatter plot with x as the horizontal axis and y as the vertical axis, obtained by measuring the carbon nanotube dispersion liquids stored at 40°C for 1 day, 40°C for 7 days, and 40°C for 14 days, respectively. The number of days elapsed by static storage is i, and the static storage temperature is 40° C. The resin composition for secondary battery is cut at 25° C. and a cutting speed of 1.0 s. -1 The shear viscosity under i (Pa·s), and the complex elastic modulus at 25°C and a frequency of 1 Hz obtained by dynamic viscoelasticity measurement is defined as G * i (Pa), x is at 25°C and cutting speed is 1.0s -1 The shear viscosity η i The natural logarithm of (Pa·s) (ln(η i )), y is the complex elastic modulus G at 25°C and frequency 1 Hz * i (Pa), i is 1, 7, and 14 when the production day of the carbon nanotube dispersion is set to day 0. ) 7 . A carbon nanotube resin composition comprising the carbon nanotube dispersion according to claim 5 and a binder resin.
8. A composite material slurry comprising the carbon nanotube dispersion as claimed in claim 5, a binder resin and an active substance.
9. An electrode membrane formed from the composite material slurry according to claim 8. 10 . A secondary battery comprising a positive electrode and a negative electrode, wherein at least one of the positive electrode and the negative electrode has the electrode film according to claim 9 .
11. A method for producing carbon nanotubes, comprising the step of dry-grinding the carbon nanotubes using a grinding device containing a grinding medium made of metal or ceramic material, wherein the dry-grinding is through-grinding or circulation-grinding, and the volume density X of the carbon nanotubes after dry-grinding is 0.095 g / cm 3 Above and 0.125g / cm 3 Hereinafter, the Zr content is 5 ppm or more and 500 ppm or less, and the maximum solvent absorption capacity Y of the carbon nanotubes defined by the following formula (5) is 8.0 or more. Y=W / V···Formula (5) (In formula (5), V is the mass (g) of the carbon nanotubes, and W is the maximum mass (g) of N-methyl-2-pyrrolidone absorbed by the carbon nanotubes when N-methyl-2-pyrrolidone is added dropwise to the carbon nanotubes of V (g) at 25°C.) 12. The method for producing carbon nanotubes according to claim 11, wherein: The rate of change between the bulk density X after dry pulverization and the bulk density X′ before dry pulverization is not less than −60% and not more than 1000%. Volume density change rate (%) = (X / X'-1) × 100 13. The method for producing carbon nanotubes according to claim 11, wherein: The rate of change between the powder resistance value Re after dry pulverization and the powder resistance value Re' before dry pulverization is 1% or more and 20% or less. Powder resistance change rate (%) = (Re / Re'-1) × 100 14. The method for producing carbon nanotubes according to claim 11, wherein: The pulverizing media are zirconia beads, and the zirconia beads have a bead diameter of more than 5 mm and less than 10 mm.
15. The method for producing carbon nanotubes according to claim 11, wherein: The average fiber length of the carbon nanotubes after the dry pulverization is 0.2 μm or more and 1.1 μm or less.
16. The method for producing carbon nanotubes according to claim 11, wherein: The carbon nanotubes after the dry pulverization have an average fiber length of 0.2 μm to 1.0 μm, and a Zr content of 15 ppm to 200 ppm. 17 . A method for producing a carbon nanotube dispersion, comprising the step of mixing and dispersing the carbon nanotube according to claim 11 , a dispersant and a non-aqueous dispersion medium.
Citation Information
Patent Citations
Method for purifying multilayered carbon nanotubes
CN104428244A
Method for preparing carbon nanotube, and dispersion composition of carbon nanotube
CN106413949A
Carbon nanotube dispersion liquid and use thereof
CN116171307A
Carbon nanotube, carbon nanotube dispersion, and utilization thereof
JP2020029372A
Carbon nanotube, carbon nanotube dispersion and their uses
JP2021095314A